Postharvest biocontrol potential and mechanisms of Fusarium tricinctum against pear black spot caused by Alternaria alternata - Yun-Feng Liu; Zheng-Yu Zhu; Na Liu; Bo-Lin Li; Xue-Li He; Yu-Xing Zhang (Postharvest Biology and Technology, 2026)

Stratigraphy, sedimentology, and palaeoenvironment of dinosaur-bearing Upper Cretaceous Zhengyang Formation in Zhengyang Basin, Chongqing, Southwest China - Hui Dai; Jun Wang; Liang-Dong Luo; Qian-Ru Wen; Su-Chin Chang; Yu Lin; Ming Xiao; Hai Xing (Palaeoworld, 2026)

DEM investigation of soil arching effect induced by vertical unloading under high geostress - Xing-Tao Lin; Ze-Yu Zhao; Dong Su; Xiangsheng Chen (Computers and Geotechnics, 2026)

Phylogenomics and morphological evidence reveal a new genus Callibractia gen. Nov. (Apiaceae, Apioideae), a distinct alpine lineage of Sino-Himalaya shaped by uplift of the Pan-Tibetan Highlands - Zi-Xuan Li; Chang Peng; Xing-Jin He; Yu-Lin Xiao; Wei-Yan Tan; Li-Jia Liu; Song-Dong Zhou (Molecular Phylogenetics and Evolution, 2026)

LiCl@NH2-MIL-88b/Ta4C3TX/graphene aerogels for efficient atmospheric water harvesting - Yi’na Yang; Tianran Zhao; Liyang Zhao; Zikun Lin; Jia Chen; Chunna Yu; Chang Zhao; Guangjian Xing (Colloids and Surfaces C: Environmental Aspects, 2026)

Molecular bridging stabilizes halide perovskites for durable photocatalytic H2 production in pure water - Xiwen Ma; Na Han; Wanying Cheng; Guiqiang Diao; Ming Sun; Shaomin Peng; Guichuan Xing; Lin Yu (Chemical Engineering Journal, 2026)

Immobilizing MIL-9 in PVDF spheres for durable and efficient peroxymonosulfate activation toward antibiotic degradation - Xing-Lin Lv; Peng Wang; Xiang-Yu Li; Fei Wang; Zi-Yu Jia; Miao Chang; Xin Jiang; Zhao-Yi Liu; Xiao-Hong Yi; Anping Wang; Jiguang Deng; Chong-Chen Wang (Chemical Engineering Journal, 2026)

Metagenomics-guided targeted isolation and mechanistic elucidation of haloalkaliphilic bisphenol A-degrading microorganisms - Sai Yang; Kai-yan Xing; Yue-fei Tao; Jia-yu Wang; Ke-hang Liu; Meng Zhang; Xiang-ru Xu; Lin Zhu; Wei Wei (Bioresource Technology, 2026)

Control efficacy of five oomycides against rapeseed clubroot disease caused by Plasmodiophora brassicae - Yuanyuan Zhang; Tiantian Li; Li Jin; Ling Jin; Yang Sun; Xing Chen; Ronghua Lin; Nan Zhang; Yu Chen (Crop Protection, 2026)

Machine-learning modeling and optimization of electro-osmotic dewatering of wastewater sludge: Current status and challenges - Xing Zhang; Yu Huang; Yafei Shi; Wei Zhang; Yuantao Lin; Jinkai Yan; Youzhou Jiao; Yalin Li (Waste Management, 2026)

Carbon dot-based catalytic materials: From photo/electrocatalysis to nanozyme activity - Pei-De Zhu; Chang Liu; Hui Wang; Rong-Yu Yao; Ling-Rui Sun; Xin-Ru Xu; Jing-Wen Jiang; Ying-Sheng Xu; Kun-Peng Lin; Jia-Xing Wu (Journal of Environmental Chemical Engineering, 2026)

Recoverable millimeter-sized poly(ether-ether-ketone)-based adsorbent beads with multisite complexation for Co2+/Ni2+ removal from radioactive wastewater - Peng-De Yu; Yan-Lin Ren; Wen-Juan Wang; Ya-Juan Cai; Ting Yue; Ke-Xiao Sang; Yi-Xing Sun; Dan Wu; Zi-Hao Yang; Chuan-Zhe Zhao; Ying-Kang Li; Ya-Ge Wu; et al. (Journal of Environmental Chemical Engineering, 2026)

Divergent activation of a glutathione-tryptophan module by cysteine and hydrogen sulfide enables metabolic recovery from cyanide poisoning in rice - Yi Kang; Xing-Hui Feng; Cheng-Zhi Li; Yu-Juan Lin; Xiao-Zhang Yu (Journal of Environmental Chemical Engineering, 2026)

N-3 PUFA deposition and esterification patterns drive aroma profile remodeling in the longissimus dorsi of pigs fed flaxseed oil - Yingsen Liu; Longzhu Zhou; Luxi Lin; Shijie Wang; Yiyu Yin; Haoyang Han; Huihui Tian; Miaomiao Dong; Pingyang Li; Youyou Yang; Xiaohui Feng; Weihai Xing; et al. (Food Chemistry, 2026)

PFAS exposure is associated with retinal neurotoxicity in Chinese adolescents: Mechanistic insights from integrated toxicogenomic and in vitro analyses - Xing-Xuan Dong; Shi-Yi Gong; Yu-Hui Hu; Gang Liang; Hua Xu; Dan-Lin Li; Yun Zhao; Chen-Wei Pan (Environmental Pollution, 2026)

Humification and greenhouse gas emissions divergently regulated during black soldier fly manure composting system by biochar, humic acid, and tea residue - Nanyi Wang; Ben Zhang; Wenjuan He; Hongmei Yin; Man Yu; Binghua Yan; Liuqin He; Lin Luo; Xi He; Lihua Zhang; Xichen Zhao; Xing Peng; et al. (Bioresource Technology, 2026)

Outdoor light at night exposure and hypertension risk in adults: A longitudinal cohort study from the FLORA project - Shuo Zhang; Xiao-Fan Lu; Muhammad Amjad; Lin-Jing Gong; Na Liu; Hong-Xing Zou; Xiao-Yi Liu; Le-Bing Wang; Yuan-Yuan Fan; Yang-Yang Li; Yi-Ran Chen; Wen-Wen Bao; et al. (Environmental Research, 2026)

Genomic mining of the terpene synthase family in magnoliids reveals novel clades - Fang Wang; Qiongqiong Lin; Zijian Zhang; Yunyang Yu; Mengxue Feng; Meixiu Lin; Yongjuan Ren; Liuming Luo; Xin Liu; Huan Liu; Sunil Kumar Sahu; Tong Wei; et al. (The Nucleus, 2026)

Model test study on instability of tunnel face affected by existing double circular tunnels - Xing-Tao Lin; Qi-Jia Wu; Hao Xiong; Dong Su; Ze-Yu Zhao; Xiangsheng Chen (Tunnelling and Underground Space Technology, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Minutes-long soft X-ray prompt emission from a compact object merger - An Li; Chen-Wei Wang; Niccolò Passaleva; Jie An; Bin-Bin Zhang; Eleonora Troja; Yi-Han Iris Yin; Yuan Liu; Shao-Lin Xiong; Li-Ping Xin; Yi-Xuan Shao; Jun Yang; et al. (Science Bulletin, 2026)

Comprehensive analysis of microbial community assembly and metabolic dynamics reveals the effects of environmental acidity on flavor formation pathways during the Zhejiang rosy vinegar fermentation process - Cheng-Hao Jin; Yong-Zhu Zhang; Wen-Tian Song; Peng Wang; Chang-Ling Wu; Lin-Mei Liang; Wei Feng; Xiao-Tao Sun; Xing-Quan Liu; Guan-Yu Fang (Food Research International, 2026)

Tolypaxillines A–J: indole diterpenoids with neuroprotective activities from a soil-derived fungus Tolypocladium album DWS131 - Yu-Fen Tan; Xing-Yi Chen; Chao Wang; Ai-Lin Liang; Wen-Yu Lu; Le-Meng Feng; Qi Huang; Yue-Ping Jiang; Shao Liu; Xiao-Bo Xia; Jing Li; Wen-Xuan Wang (Phytochemistry, 2026)

Green synthesized Cu2O/TiO2 nanotube heterojunction for pharmaceutical mineralization and simultaneous hydrogen evolution: mechanistic insight and toxicity assessment - Fang-Yu Liang; Dong-Ni Wu; Wan-Chun Lin; Yi-Ching Lin; Chia-En Tsai; Chia-Hua Lin; Wu-Xing Chen; Chia-Hung Chen; Yen-Ping Peng (Journal of Environmental Management, 2026)

The potential mechanism of nitrous oxide accumulation in wastewater treatment plants under different load conditions - Wen-Jiao Sang; Bing Gong; Chong-Yang Xing; Bei-Bei Chen; Zhi-Lin Zhang; Hui-Min Fu; Ya-Song Chen; Wan Sun; Meng-Meng Liu; Shun-Li Cheng; Yu-Lin Wang; Qiang Wang; et al. (International Biodeterioration & Biodegradation, 2026)

Root-mediated oxygen transfer drives Methylobacter enrichment and secondary alcohol metabolism to strengthen chlorobenzene degradation in landfill rhizosphere systems - Liang-jie Li; Yu-fan Liu; Zhi-lin Xing; Kun Cao; Tian-tao Zhao (Biomass and Bioenergy, 2026)

Enhancing Ore Recovery and Profitability Through Blast-Aware Dig-Limit Optimization in Open-Pit Mining - Zhi Yu; Lin-Feng Du; Zong-Xian Zhang; Ming-Qing Huang; Jian-Hua Hu; Jian Zhou; Xing-Qi Cai (Rock Mechanics and Rock Engineering, 2026)

Genome-wide identification of the MYB transcription factor family of blackcurrant and the key role of RnMYB44 gene in drought tolerance - Lin Wang; Xuelin Zhang; Xueying Zhao; Hongyinga Li; Jiacheng Liu; Yu Zheng; Zongya Xing; Huixin Gang; Junwei Huo; Dong Qin (Planta, 2026)

Exploration and Development Site Selection of Marine Sand Resources Around Hainan Island, China: An Integrated Analysis Based on a Combination of Subjective and Objective Weights - Maogang Qin; Changliang Tong; Mingzhi Lin; Bo Chen; Jialin Wang; Jun Zhu; Mingkun Lin; Yu Zhu; Xing Huang (Natural Resources Research, 2026)

Virulensome: a transient organelle mediating fungal virulence - Pei-Ji Zhao; Qian-Yi Hu; Si-Han Wang; Cheng-Song Wang; Xue-Xian Jian; Xing-Fu Wen; Yu-Lin Luo; Ya-Qi Zhang; Chun-Mei Xiang; Guo-Hong Li; Shu-Qun Liu; Ming-He Mo; et al. (Science China Life Sciences, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Mechanically engineered multi-oxide heterojunctions for bifunctional antibacterial and photocatalytic environmental remediation - Juan Pei; Jialan Mi; Shuhan Yao; Mingxing Guo; Ye Zhang; Xiaoling Wan; Wei Wu; Ying Hong; Pei Hu; Ping Chen; Lin Chen; Haichun Zeng; et al. (Journal of Environmental Chemical Engineering, 2026)

Efficient hydrolysis of glycosides by Pichia kudriavzevii with high-activity β-glucosidase: a critical role in enhancing terpene aroma in beer - Lin Yuan; Xiaoping Hou; Yang He; Xiujuan Wan; Jiaxin Han; Wenqi Xu; Shuo Yu; Shuang Bi; Lijuan Ma; Lei Xing (Food Chemistry, 2026)

DiTing v2.0: A Snakemake-Optimized Workflow for Multi-Omics-Based Biogeochemical Pathway Analysis - Xing Chen; Heyu Lin; Chunxu Xue; Yi Liu; Jiwen Liu; Min Yu; Xiaolei Wang; Xiaohua Zhang (Journal of Ocean University of China, 2026)

AI-driven discovery of natural product-derived FAK1 inhibitors for idiopathic pulmonary fibrosis - Xing-Yi Chen; Mei-Hong Lu; Bin Li; Ya Zhou; Li Liu; Hao Yang; Qiu-Yu Wang; Lin Chang; Yu-Lan Zhao; Dong-Mei Wang; Bin Li; Ben-Rong Mu (Molecular Diversity, 2026)

Discovery of anti-glioblastoma natural products based on andrographolide derivatives: efficiently identifying potential multi-target and multifunctional molecules through the integration of in silico methods and experimental verification - Ya-Lin Li; Jun Mao; Xin-Yu Zhou; Duan-Na Zhang; Yu-Zhi Li; Zhi-Xing Cao; Ji-Xia Ren (Molecular Diversity, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Cation-anion synergistic interactions in ion-regulated cholesteric liquid crystal Hydroxypropyl methylcellulose coatings for lithium metal batteries - Zhanpeng Du; Yun Huang; Fengliang Wang; Lei Zhang; Jing Tao; Jin Bao; Heguo Zeng; Jiajun He; Huihui Li; Chao Zou; Chunmei Feng; Bingshu Guo; et al. (Chemical Engineering Journal, 2026)

Sustained performance and microbial succession in novel artificial rumen system coupling dynamic membrane with methanogenic granules for acid absorption - Xiang-Lin Chang; Bao-Shan Xing; Yu Qin; Juan Xie; Zhi-Bo Li; Xiaochang C. Wang; Rong Chen; Yu-You Li (Bioresource Technology, 2026)

Anoikis-Related Genes Can Accurately Predict the Occurrence of Endometriosis: A Retrospective Cohort Study via Machine Learning Analysis - Lin Hong; Lan Zheng; Yu-Feng He; Ya-Xing Fang; Hui Chen; Kang-Jia Chen; Shu-Guang Zhou (Biochemical Genetics, 2026)
Endometriosis is one of the most common benign gynecological disorders, characterized by persistent pain and challenges with fertility. Anoikis, a specific form of apoptosis, occurs when cells detach from the extracellular matrix. Recent researches have revealed that anoikis resistance is the most important prerequisite for endometriosis development, but it's still not entirely apparent, yet, what part anoikis plays in endometriosis pathogenesis. We obtained the GSE141549 dataset from the GEO database, which served as our training cohort. Anoikis-related genes (ANRGs), sourced from the GeneCards database, were integrated with differentially expressed genes (DEGs) identified in GSE141549. Consequently, we obtained a collection of differentially expressed anoikis-related genes (DE-ANRGs). Subsequently, we employed machine learning algorithms to screen for key diagnostic DE-ANRGs and developed a nomogram model to predict and diagnose endometriosis. Ultimately, we validated our findings through in vitro experiments and an online endometriosis database. Within the training cohort, a total of 47 DE-ANRGs were identified. Furthermore, three machine learning methods pinpointed four diagnostic genes (CAV1, PDK4, CSPG4, SERPINE1). Based on these genes, we constructed a nomogram to facilitate the prediction and clinical diagnosis of endometriosis. To assess model's predictive accuracy, clinical adaptability, and discriminative ability. We performed calibration curves, Receiver Operating Characteristic curves and decision curve analysis. All assessments demonstrated our model's outstanding performance. Ultimately, consistent expression trends of four genes were observed in GSE7305 test cohort, clinical specimens, and the Turku database when compared to the training cohort. In addition, we also have revealed the immune landscape differences, which may offer new promising immunotherapeutic targets for endometriosis patients in the future. In addition to offering novel perspectives on the role of anoikis in endometriosis pathogenesis, our analysis also identified a panel of distinctive biomarkers with significant diagnostic potential. Graphical abstract

Integrated LC-Orbitrap-MS and network pharmacology decipher the pharmacological basis of Eucommiae folium in treating rheumatoid arthritis - Yasi Deng; Ling Liang; Haokai Lin; Xinyang Shen; Hao Zheng; Ying Deng; Xing Tian; Juan Huang; Ye Zhang; Bin Li; Huanghe Yu; Wei Wang (Molecular Diversity, 2026)

Intercropping significantly elevates carbon sequestration by mitigating the decline in soil total carbon caused by excessive phosphorus-application - Chuan-Lin Xiao; Ran An; Jiu-Dong Zhang; Yi Xing; Xing-Guo Bao; Rui-Peng Yu; Hans Lambers; Xiang Wang; Long Li (Soil and Tillage Research, 2026)

Tilapia skin collagen peptides‑calcium chelates:Structural characterization, stability, in vitro and in vivo anti-osteoporosis mechanism - Xing Xie; Meng-ting Zhang; Chun-lin Huang; Jin-yu Wang; Qiao Ding; Yan-xia Xiong; Zong-cai Tu; Lu Zhang (Food Research International, 2026)

Isolation and identification of spoilage bacteria from kiwifruit and analysis of the antagonistic activity of three Bacillus strains against these bacteria - Ang Liu; Wen-xin Li; Yi Liu; Xing-lin Ran; Bo-yu Dong; Qiu-ping Yao; De-quan Zhu (Food Control, 2026)

Alpha-ketoglutarate restores oral epithelial homeostasis via FOXM1-mediated cell cycle regulation - Yuan Wang; Yimeng Cai; Qi Yin; Shuqin Cao; Yuyu Li; Yuhan Li; Qiwen Li; Qian Wang; Pochun Lin; Li Mei; Malcolm Xing; Leixiao Yu; et al. (Science China Life Sciences, 2026)

Coupled effects of straw return practices on soil microbial functional potential and agricultural productivity in Semi-Arid Region - Rui-Zhi Liu; Xiao-Ya Zhao; Li-Jie Wang; Xing Zhang; Shu‑Ping Hu; Ju‑Lin Gao; Xiao‑Fang Yu; Qinggeer Borjigin (Plant and Soil, 2026)

A New Species of Diaporthe Section Betulicola (Diaporthomycetidae, Diaporthales) From China - Yi Lan Jin; Xing Yu Luo; Kamran Habib; Yu Lin Ren; Qing Yang; Li Li Liu; Chanhom Loinheuang; Yang Chen; Qi Rui Li (New Zealand Journal of Botany, 2026)
A new species in Diaporthaceae, Diaporthe fengtaiensis sp. nov., is described and illustrated from Southwestern China. A comparative morpho‐anatomical study and multilocus phylogenetic analysis (ITS, CAL , HIS , TEF1‐α , TUB2 ) confirmed its position within the section Betulicola of the genus Diaporthe . The taxon is characterized by immersed ascomata (270–420 × 290–410 µm), relatively large asci (70–115 × 9.5–13.5 µm), and 1‐septate, fusiform ascospores (18.5–25.6 × 4.5–6.5 µm). Its positioning in a separate branch in the phylogenetic tree makes it distinct from the other known species of the section. A complete taxonomic treatment, based on two collected specimens, is provided along with molecular phylogenetic analyses.

The interplay between antihypertensive medication and lifestyle with cardiovascular outcomes in patients with hypertension: the PURE-China study - Biyan Wang; Zhiguang Liu; Tong Bu; Sumathy Rangarajan; Qiuyan Ma; Xiaocong Li; Qi Qiu; Yang Lin; Lap Ah Tse; Bo Hu; Salim Yusuf; Qiujing Cai; et al. (EPMA Journal, 2026)

An efficient strategy to separate nanoplastics from water using anisotropic magnetic Janus particles - Ruiqi Yan; Sen Lin; Xia Yu; Lei Zhang; Jiaxi Wang; Wentao Zhao; Mingyang Xing; Qian Sui (Water Research, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Water quality and biofilm growth in drinking water distribution systems with the low-dose sodium hypochlorite disinfection after ultrafiltration pretreatment - Yu Zhou; Kangbing Zou; Xiaokai Wang; Zhihong Wang; Wei Song; Xing Du; Dachao Lin (Journal of Environmental Sciences, 2026)

Effective recovering Pd(II) ions via tuning the Lewis basicity of nanofiber capture vacancy - Nianshou Cheng; Mingyue Wang; Lu Wang; Lin Zhang; Chuanbin Li; Yu Guo; Bo Xing; Haichao Wang; Min Li (Journal of Environmental Sciences, 2026)

Manganese cycle-mediated synchronous bacteria-algae/anammox coupled denitrification system under low-temperature conditions: Performance and mechanisms - Peng-fei Yu; Dian-lin Jiang; Ding Wang; Xing-guan Ma; Jun-Li; Li-yao Han; Ao Wang; Yu-bo Fu; Xing Jin (Bioresource Technology, 2026)

Identification of low-toxicity DNA topoisomerase I inhibitors with potential blood–brain barrier penetrability for glioblastoma therapy: structure-based virtual screening reveals promising novel Scaffolds - Ya-Lin Li; Jun Mao; Zhong Cheng; Xin-Yu Zhou; Duan-Na Zhang; Yu-Zhi Li; Zhi-Xing Cao; Ji-Xia Ren (Molecular Diversity, 2026)

piR-16404 drives ferroptotic liver injury via CASTOR1/mTORC1/GPX4 dysregulation in HepG2 cells and mice: a novel toxicity mechanism of N, N-dimethylformamide - Wanli Ma; Xiaoyu Huo; Ruoxi Li; Jingjing Xing; Lin Xu; Dianke Yu (Archives of Toxicology, 2026)

Two new clerodane diterpenoids and their anti-inflammatory activity from Callicarpa integerrima - Muhammad Aurang Zeb; Xiao-Ying Ruan; Xing-Jie Zhang; Yu-Tong Xing; Meng-Ru Wang; Yuan-Lin Kong; Xiao-Li Li; Kai Jiang; Wei-Lie Xiao (Natural Product Research, 2026)

AEG-1/MTDH Enhances Hepatocellular Carcinoma Radioresistance by Recruiting PTBP1 Via SND1 To Stabilize ATG5 mRNA and Promote Protective Autophagy - Xiaochun Chen; Yu Wang; Qishuai Guo; Xing Lin; Zhiping Yuan; Wei Liu; Chuan Lin; Yongjun Li; Yongpeng He (Cell Biochemistry and Biophysics, 2026)

Experimental study on failure mechanism of tunnel face during shield tunneling beneath existing underground rectangular structure - Xing-Tao Lin; Qi-Jia Wu; Liqiang Cao; Ze-Yu Zhao; Dong Su; Xiangsheng Chen (Tunnelling and Underground Space Technology, 2026)

Mechanisms of organic matter accumulation during Early Silurian carbon-cycle perturbations: Geochemical constraints from the inner shelf, Upper Yangtze, South China - Weizhen Chen; Jingchun Tian; Xiaobing Lin; Kailong Feng; Qingshao Liang; Wei Yu; Xing Wang; Shi Sun (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

An efficient framework of nonlinear hysteresis analysis for multi-bolt connections via improved Iwan model and CG-FFT - Tengfei Wu; Jian Xing; Qiangqiang Zhao; Dewen Yu; Qiyin Lin; Jie Xiao; Jun Hong (Engineering Structures, 2026)

Hyperbranched polyamine-graft-poly(ε-caprolactone) with integrated flame retardancy, plasticization, and filler-dispersion functions toward high-performance poly(vinyl chloride) plastics - Xing-Hao Wang; Liang Yang; Jing Zhao; Ze-Zhong Lin; Dan-Dan Shi; Yu Chen; Pei-Yao Chen (Chemical Engineering Journal, 2026)

Pulsed electric fields as a green alternative to chemical treatment: Toward enhanced molecular interactions and performance in biodegradable preservation films - Rui Wang; Pei-Feng Guo; Ying Xu; Xing-Chan Xie; Dan-Dan Lin; Yu-Wei Wu; Dong-Yang Xu; Lang-Hong Wang; Xin-An Zeng (Chemical Engineering Journal, 2026)

Tetramethylpyrazine-caffeic Acid Hybrid CT-011 Exerts Dopaminergic Neuroprotection Through Inhibiting Microglia-mediated Neuroinflammation - Min Xie; Yu Cheng; Lizhen Yang; Zijin Lin; Hao Shen; Xinhua Zhou; Zheng Liu; Jieyu Xing; Sigui Zhou; Haiyun Chen (Molecular Neurobiology, 2026)

Analysis of clinical characteristics and prognostic factors in AIDS complicated by cryptococcal meningitis - Yanlan Liang; Xiyang Dong; Yong Deng; Zhende Lin; Caixia Zheng; Jiaxuan Li; Yijie Lin; Huatang Zhang; Xing Wang; Wenwu Lin; Wencong Hong; Su Zhang; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Cassane diterpenoids with hepatic gluconeogenesis inhibitory activity from the seeds of Caesalpinia decapetala (Roth) Alston - De-Sheng Wang; Yu Shen; Lin-Fen Ding; Run-Cheng Yan; Ming Hu; Wen-Chao Tu; Liu-Dong Song; Suling Huang; Xing-De Wu (Phytochemistry, 2025)

A unified framework for predicting vertical bearing capacity of fully embedded pipes/tunnels in clay seabed based on the undrained failure mechanisms - Yu Zhao; Xing-Tao Lin; Wei-Jian Li; Jun-Chen Zhang; Zhi-Yao Tian; Quan-Mei Gong (Ocean Engineering, 2025)

Advances in the research on phenolic acids and flavonoids in vinegar: Sources, formation and degradation mechanisms, and functional properties - Cheng-Hao Jin; Yong-Zhu Zhang; Feng-Hua Wu; Chang-Ling Wu; Peng Wang; Wei Feng; Lin-Mei Liang; Wei-Jiang Xu; Xiao-Tao Sun; Xing-Quan Liu; Guan-Yu Fang (Food Research International, 2025)

Astaxanthin enhances broiler health via integrated regulation of antioxidant capacity, immune function, and gut microbiota - Xiao-Ming Gu; Ding-Cheng Ye; Jun-Wei Cheng; Zhi-Xin Lin; Hai-Xuan Lv; Zai-Xing Cai; Yun Yang; Chang-Kang Wang; Yu-Yun Gao; Ling Jin (Food Chemistry, 2025)

Rapid and sensitive on-site detection of peach (Prunus persica) species in fruit juices using a RAA-CRISPR/Cas12a approach - Lin Wang; Ran-Ran Xing; Xiao-Ke Liang; Yao-Xian Yu; Qiu-Ju Yi; Si-Yuan Lu; Ting-Ting Deng; Jiu-Kai Zhang; Xu Wang; Ying Chen (Food Control, 2025)

A novel Halo Tag-based photo-crosslinking system for efficient drug target identification via chemoproteomic profiling - Xing Liu; Wenjing Ji; Yulin Tao; Yuxiang Gong; Qiannan Zhang; Ruoyao Lin; Yang Yang; Yiting Wang; Shasha Li; Yu Zhang; Hongli Liu; Zhixiang Du; et al. (Analytica Chimica Acta, 2025)

Real-world emissions and total output from fishing vessels in Taiwan - Po-Yen Chien; Chia-Hsiang Lai; Wu-Xing Chen; Chia-Hung Chen; Chia C. Wang; Amila Kasun Abeysinghe; Yi-Ching Lin; Tsai-Jung Yen; Hsiang-Ying Wu; Yu-Lun Tseng; Pei-Shih Chen; Yen-Ping Peng (Transportation Research Part D: Transport and Environment, 2025)

Hypoglycemic cucurbitane-type triterpenoids from fruits of Citrullus colocynthis - Hua-Wei Lv; Yu Wan; Wen-Lin Fan; Meng-Di Zhu; Qiao-Liang Wang; Zhong-Bo Zhou; Chang-Chun Chen; Hong Wang; Xing-Nuo Li (Phytochemistry, 2025)

Efficient and selective separation of uranium(VI) from natural waters by MgAl-LDH/CNT composites: Performance evaluation and adsorption mechanism - Jianchun Qin; Wenlin Zhao; Wensheng Zhao; Gao Cheng; Xiuxian Huang; Yuan Liu; Jiebing He; Xing Wei; Shunyan Ning; Lin Yu (Journal of Water Process Engineering, 2025)

Integrating geological indicators for enhanced mapping of soil organic matter in hilly landscapes - Shuangshuang Shao; Liping Li; Lin Yang; Baowei Su; Huan Zhang; Chao Gao; Likun Gu; Yalu Zhang; Weiqin Xing; Mingyu Yu (Journal of Cleaner Production, 2025)

A dynamic prediction model for maximum lateral displacement of foundation pit enclosure structure using multi-source fusion method - He Wei Kuang; Zhi Yong Ai; Gan Lin Gu; Hong Wei Huang; Zeng Zhi Qian; Da Xing Zhou; Yu Xin Zhai; Hai Feng Guo (Computers and Geotechnics, 2025)

Mechanochemical synthesis of ZnO@TiO2 II heterojunction material: Photocatalytic degradation and antibacterial synergistic effect - Juan Pei; Xiaoling Wan; Mingxing Guo; Jialan Mi; Wei Wu; Ying Hong; Pei Hu; Ping Chen; Lin Chen; Siwei Xiang; Qianyu Zhang; Haichun Zeng; et al. (Chemical Engineering Journal, 2025)

Aluminum exposure disturbs epigenetic modification and organelle function during early embryo development - Xiao-Ting Yu; Zhen-Hui Fu; Wen-Lin Pan; Yan-Lun Song; Rui-Jie Ma; Hao-Lin Zhang; Xing-He Ke; Shao-Chen Sun; Jun-Li Wang; Lin-Lin Hu (Chemico-Biological Interactions, 2025)

The recovery mechanism of granular sludge fragmentation and re-granulation caused by long-term high-concentration organic matter erosion in the SAD process: performance, sludge evolution, and metagenomic sequencing - Peng-fei Yu; Ding Wang; Yu-bo Fu; Xing-guan Ma; Hao Zheng; Li-yao Han; Ao Wang; Dian-lin Jiang; Hai-wen Sun; Xing Jin (Bioresource Technology, 2025)

The influence of water flow disturbance form on the granulation of algae sludge: Granulation property, treatment effect and algae biological structure - Peng-fei Yu; Ao Wang; Hai-wen Sun; Ding Wang; Xing-guan Ma; Yu-jia Wang; Bo-mei Hu; Li-yao Han; Yu-bo Fu; Dian-lin Jiang; Shi-gang Tu (Journal of Water Process Engineering, 2025)

A novel esterase MfdS catalyzes ester bond cleavage and promotes the degradation of mefenpyr-diethyl by Hansschlegelia zhihuaiae S113 - Houyu Yu; Rongrong Zhang; Lin Lai; JingJing Liang; Thamer Y. Mutter; Xing Huang (Journal of Environmental Chemical Engineering, 2025)

Effects of puerarin on growth performance, digestive ability, immune response, and resistance to ammonia stress in Pacific white shrimp (Litopenaeus vannamei) in low-salinity water - Yu-Lin Chang; Long Qi; Chao-Li Guan; Yu-Yun He; Wen-Xing Lu; Guo-Fang Zhong (Fish & Shellfish Immunology, 2025)

System characteristics of integrated continuous flow simultaneous partial Nitrification, Anammox and Denitrification (SNAD) for NH4+-rich wastewater: performance, sludge evolution, metagenomic sequencing analysis - Peng-fei Yu; Ding Wang; Xing-guan Ma; Yu-bo Fu; Li-yao Han; Ao Wang; Dian-lin Jiang; Hai-wen Sun; Dong-xue Li; Xing Jin; Kang-da Yang; Li-cheng Zhang; et al. (Environmental Research, 2025)

Development of a multifunctional and biocompatible hydrogel for flexible implantable sensors - Kaiqi Zhang; Huibiao You; Yuxi Liu; Fulei Lin; Yanan Li; Lina Jia; Jinxiao Bao; Xin Ge; Gaofei Pan; Huitao Yu; Ruiguang Xing (Chemical Engineering Journal, 2025)

Spatial–Temporal Dynamics of Drought Characteristics and Its Influencing Factors on Tibetan Plateau - Zhizhu Zhou; Wenjun Yu; Lin Zhao; Yanzhong Li; Shuo Cheng; Jiazhe Duan; Yincong Xing; Wei Shao (International Journal of Climatology, 2025)
Assessing drought on the Tibetan Plateau (TP) is essential for understanding the spatial characteristics of the region's hydrological regimes, as well as the trends of the evolving climate‐ecological system. Based on the precipitation and the potential evapotranspiration data from the ERA5‐Land dataset, this study evaluated the drought characteristics on the TP from 1950 to 2022 using the Standardised Precipitation Evapotranspiration Index (SPEI) and the Run theory. The analysis of SPEI at multiple time scales—SPEI‐1 (monthly), SPEI‐3 (seasonal), and SPEI‐12 (annual)—consistently revealed a pronounced drying trend across the TP over the past 70 years. Notably, the wet‐to‐dry transition points were detected in 2000 and 2001 based on the SPEI‐1 and SPEI‐3 series, respectively, while the SPEI‐12 series indicated a later shift occurring in 2004. In addition, the SPEI values indicated a spatial trend of increasingly severe drought conditions from south to north. Particularly, pronounced drought stress was observed in the Brahmaputra, Ganges, and Indus basins, as well as in the southern regions of the Inner Plateau. Furthermore, the relationships between drought variability and key climatic drivers—including sunspots, El Niño‐Southern Oscillation (ENSO), temperature (TEMP), and annual mean areal precipitation (AP)—were identified through cross‐wavelet transform (XWT) and wavelet coherence analysis (WTC). In general, the analysis showed that the SPEI values on the TP were negatively correlated to ENSO and TEMP but positively correlated to sunspots and AP. This study offers a comprehensive spatiotemporal assessment of drought dynamics across the TP, providing critical insights for regional water resource management and climate change adaptation planning.

Geological Structural Characteristics of Subashi in West Kunlun Revealed by Aero Geophysical and Remote Sensing Data - Ming Wang; Yi-chuan Li; Hai-qing Wang; Yan-yan Wei; Xiao-xing Lin; Dao-qing Zhou; Jin-zhong Yang; Chang Zhong; Chang-chun Yu (Applied Geophysics, 2025)

Potential impact of marine-derived plastisphere as a Vibrio carrier on marine ecosystems: Current status and future perspectives - Xuemei Sun; Andy M. Booth; Qi Sui; Lin Zhu; Yongxiang Yu; Bin Xia; Shunlong Meng; Baoshan Xing (Journal of Hazardous Materials, 2025)

Using ventilation hood during cooking reduced household air pollution exposure and brought cardiometabolic and pulmonary health benefits: A community-based, cluster-randomized controlled intervention study - Yueru Yang; Kuai Yu; Wending Li; Xuedan Xu; Chengyong Jia; Qi Yan; Xingxing Li; Hao Cai; Denghuan Hu; Hui Gao; Xuanwen Mu; Yuhui Lin; et al. (Journal of Hazardous Materials, 2025)

Feasibility of a hybrid AHA-GPR model for predicting blasting fragmention in surface mines - Zhi Yu; Lin-Feng Du; Jian-Xing Liu; Jian Zhou; Chuan-Qi Li (Earth Science Informatics, 2025)

Aurantibrevibacter litoralis gen. nov. sp. nov. a Novel Member in the Family Flavobacteriaceae Isolated from Sediment of Tidal Flat Located in Ningbo, China - Yun-Fei Cao; Dong-Yan He; Yu-Ruo Wang; Ke Cao; Yang Li; Jia-Wei Gao; Xing-Cheng Wang; Lin Xu; Cong Sun; Xiao-Yun Yu (Current Microbiology, 2025)

Influence of disaccharide and mixed starter cultures on the fermentation process in earthen jar of factory-produced Sichuan paocai - Qiu Zhong; Hua Xiong; Shengshuai Li; Kaiyu Guo; Yue Shu; Xia Lin; Yage Xing; Ziwei Liang; Xingchen Liu; Lei Liu; Yu Rao (Food Research International, 2025)

Recommendations of Stable Mg, Si, V, Fe, Cu, Zn, Rb, Sr, Ag, Cd, Ba, and U Isotope Compositions for Multiple Geological References - Jinting Kang; Xuqi Chen; Xi Deng; Yuan Fang; Haichuan Jiang; Chengyihong Liu; Cuihua Luo; Xing Li; Yuchao Lin; Zhaoqi Ren; Jiaru Sheng; Xue Tang; et al. (Journal of Earth Science, 2025)

pH-responsive drug-targeted delivery system: Dual-drug loading hollow mesoporous silica for synergistic therapy bacterial enteritis of Micropterus salmoides - Yuan-shuai Fu; Yue Lin; Wen-jun Zhong; Xing-yu Wang; Xi-ke Li; Yun-ao Li; Sheng-bo Ye; Wen-juan Li; Yong-heng Zhu (Chemical Engineering Journal, 2025)

Coptisine inhibits esophageal carcinoma growth by modulating pyroptosis via inhibition of HGF/c-Met signaling - Chunmei Qian; Xing Zhang; Yu-Shi Tian; Lin Yuan; Qiao Wei; Yifu Yang; Midie Xu; Xiaoyu Wang; Menghong Sun (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Motion control of negative-lift AUV based on disturbance compensation nonlinear model predictive control with extended state observation - Lin Lunyang; Chen Yuxiang; Yu Chunliang; Zhu Hong; Xiong Hong; Xing Yiyang; Zheng Guodong (Ocean Engineering, 2025)

Application of gravity gradient measurement in the detection of urban underground space - Zhong-kun Qiao; Jia-jun Zhang; Peng Yuan; Lin-ling Li; Ruo Hu; Hai-xiang Yang; Kan-xing Weng; Zong-yu Zhang; Lin-fei Wang; Pei Qin; Liang-liang Hao; Chuan Yang; et al. (Journal of Applied Geophysics, 2025)

Reliable electrochemical ratiometric sensing based on diazotization/Schiff base reaction for accurate detection of alpha-fetoprotein - Miao Wang; Xing-Yu Liu; Lin-Xiao Zhao; Zi-Wen Cui; Shan-Shan Li (Chemical Engineering Journal, 2025)

Impact of Faba Bean (Vicia faba L.) Diet and Subsequent Withdrawal on GIFT Tilapia (Oreochromis niloticus) Muscle Quality - Guanling Xu; Wei Xing; Tieliang Li; Shibo Wei; Ying Zhang; Tingting Song; Huanhuan Yu; Lin Luo (Fishes, 2025)
To systematically evaluate FB’s effects on tilapia muscle quality, two distinct experimental phases are designed, the crispy texture development phase (0–16 weeks) and the crispy texture retention phase (17–24 weeks), which can determine the minimum faba bean (FB) feeding duration required to achieve optimal textural modification and can assess the persistence of improved textural properties following FB withdrawal, respectively. The results demonstrated that a 60% FB inclusion diet administered for 16 weeks did not adversely affect tilapia growth performance. Significant improvements in textural parameters, including hardness, springiness, chewiness, and shear force, were observed in FB-fed tilapia as early as 8 weeks, with these enhancements being maintained throughout the 16-week feeding period. These superior textural characteristics persisted during the subsequent retention phase following FB withdrawal. Microstructural analysis revealed that the 60% FB diet significantly enhanced muscle-fiber density while reducing fiber diameter in tilapia during the 8–16 week feeding period. These microstructural modifications persisted throughout the texture retention phase, maintaining significant differences compared to the control group. Serological analysis demonstrated the FB group elevated Superoxide dismutase (SOD) activity and reduced malondialdehyde (MDA) levels at 4 weeks, though these differences normalized thereafter. qRT-PCR showed the 60% FB clearly increased the expression of mstn at 8 weeks, while col1a-2 and myog expressions also obviously improved at 12 weeks. In summary, dietary 60% FB improved tilapia muscle crispiness by altering texture and microstructure via gene-expression regulation. The minimum duration was 8 weeks to achieve crispiness in tilapia by the 60% FB diet without adverse effects on growth, immunity, and hepatopancreas function. Furthermore, the crispy texture of tilapia fillets was maintained for at least 2 months following withdrawal of the 60% FB diet after 16 weeks of continuous feeding.

Full realization of the RIBLL2 separator at the HIRFL-CSR facility - Xiao-Dong Xu; Yong Zheng; Zhi-Yu Sun; Yu-Nan Song; Bao-Hua Sun; Satoru Terashima; Chang-Jian Wang; Ge Guo; Guang-Shuai Li; Xiu-Lin Wei; Jun-Yao Xu; Ji-Chao Zhang; et al. (Science Bulletin, 2025)

Nano Sim@ZIF8@PDA modified injectable temperature sensitive nanocomposite hydrogel for photothermal/drug therapy for peri-implantitis - Dingkun Liu; Jinbing Chen; Linjuan Gao; Xing Chen; Liujun Lin; Yuan Liu; Xia Wei; Yu Pan; Yinghui Wang; Hui Cheng (Carbohydrate Polymers, 2025)

Reversal of Extreme Drought-Induced Plant Nitrogen and Phosphorus Imbalances in Grassland - Xiao-Sa Liang; Zheng-Wen Wang; Wentao Luo; Lin Song; Wang Ma; Niwu Te; Qiang Yu; Xing-Guo Han; Xiao-Tao Lü (Ecosystems, 2025)

NAT10 primes a post-transcriptional repertoire essential for the maintenance of spermatogonial homeostasis - Xiaoli Zhu; Caoling Xu; Xue Jiang; Jiaqi Zou; Wenqing Li; Xuemei Xing; Xiaoxiao Gao; Jiao Lei; Fei Meng; Xin Wang; Yuzhang Zhu; Yu Cheng; et al. (Science Bulletin, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Plant diversity increases diversity and network complexity rather than alters community assembly processes of leaf-associated fungi in a subtropical forest - Jie Li; Xing-Chun Li; Hui-Yun Gan; Yue Zhang; Zi-Xuan Guo; Yu-Xuan Liu; Yong-Qing Lin; Liang-Dong Guo (Science China Life Sciences, 2025)

Curculigoside Regulates Apoptosis and Oxidative Stress Against Spinal Cord Injury by Modulating the Nrf-2/NQO-1 Signaling Pathway In Vitro and In Vivo - Yu Hou; Chaolun Liang; Lili Sui; Yang Li; Kai Wang; Xing Li; Kunrui Zheng; Haitao Su; Dianweng Xie; Dingkun Lin; Da Guo; Le Wang (Molecular Neurobiology, 2025)

Bayesian-based Full Waveform Inversion - Huai-shan Liu; Yu-zhao Lin; Lei Xing; He-hao Tang; Jing-hao Li (Applied Geophysics, 2025)

Hydrodynamics Model Identification and Model-Based Control Application of a New Type of AUV - Lunyang Lin; Yuxiang Chen; Hong Xiong; Chunliang Yu; Hong Zhu; Yiyang Xing; Guodong Zheng (Journal of Marine Science and Engineering, 2025)
The hydrodynamic coefficients of underwater robots can be used to evaluate their maneuverability and motion stability and to design motion controllers, thereby reducing experimental time and costs. In this paper, an Autonomous Underwater Vehicle (AUV) with a negative-lift profile is designed. The spatially constrained motion method, combined with neural networks, is utilized to identify all the hydrodynamic coefficients in the standard hydrodynamic equations of the AUV. Subsequently, based on the goodness-of-fit, the significance of the hydrodynamic coefficients is evaluated to yield a simplified hydrodynamic equation. Given the cost constraints, it was not feasible to obtain precise experimental data on hydrodynamic coefficients to validate the accuracy of the CFD calculation method. Therefore, the hydrodynamic coefficients were used to construct a dynamic model for the AUV, and an MPC controller was designed based on this model. Finally, simulations and pool tests were conducted on the AUV, and a comparative analysis of the simulation results with the pool test results revealed that although there were certain errors in the calculation of the hydrodynamic coefficients, the controller constructed within this margin of error was still capable of effectively controlling the AUV. This fully demonstrates the feasibility and applicability of using CFD methods to calculate hydrodynamic coefficients and establishing model predictive control methods based on these coefficients in practical applications.

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Plasma proteomics identifies proteins and pathways associated with incident depression in 46,165 adults - Jujiao Kang; Liu Yang; Tianye Jia; Wei Zhang; Lin-Bo Wang; Yu-Jie Zhao; Jia You; Yue-Ting Deng; Yi-Jun Ge; Wei-Shi Liu; Yi Zhang; Yi-Lin Chen; et al. (Science Bulletin, 2025)

Cis-regulation of the CYP6CS1 gene and its role in mediating cross-resistance in a pymetrozine-resistant strain of Nilaparvata lugens - Pin-Xuan Lin; Yu-Xuan Peng; Ji-Yang Xing; Zhao-Yu Liu; Fang-Rui Guo; Joshua A. Thia; Cong-Fen Gao; Shun-Fan Wu (Insect Biochemistry and Molecular Biology, 2025)

A super convenient and specific CRISPR/Cas12a diagnostic platform for toxigenic Burkholderia gladioli based on virulence genes - Yu Xie; Li Liu; Xue-Ming Cao; Zuo-Qi Gai; Xu Zhang; Hong-Tao Lei; Zhen-Lin Xu; Xing Shen (Food Control, 2025)

RGS22 maintains the physiological function of ependymal cells to prevent hydrocephalus - Xue Pang; Lin Gu; Qiu-Ying Han; Jia-Qing Xing; Ming Zhao; Shao-Yi Huang; Jun-Xi Yi; Jie Pan; Hao Hong; Wen Xue; Xue-Qing Zhou; Zhi-Hui Su; et al. (Science China Life Sciences, 2025)

Characteristics of Tylvalosin Tartrate Enteric Amorphous Pellets Prepared by Liquid Layering - Haoran Wang; Lin Han; Han Zeng; Mengyao Yu; Tian Yin; Yu Zhang; Haibing He; Jingxin Gou; Xing Tang (Pharmaceutical Research, 2025)

Integrating sentinel-2a imagery, DEM data, and spectral feature analysis for landslide detection via fully convolutional networks - Yu Qu; Hanfa Xing; Lin Sun; Xian Shi; Jianfeng Huang; Zurui Ao; Zexiu Chang; Jiaju Li (Landslides, 2025)

Experimental investigation of the mechanical behaviour of sand-rubber-gravel mixtures - Gaochao Lin; Wei Liu; Fang Yang; He Wang; Xiaozheng Cui; Xing Su; Sichun Yu; Jiasheng Lian (Bulletin of Engineering Geology and the Environment, 2025)

A new late-diverging non-hadrosaurid hadrosauroid (Dinosauria: Ornithopoda) from southwest China: Support for interchange of dinosaur faunas across East Asia during the Late Cretaceous - Hui Dai; Qingyu Ma; Can Xiong; Yu Lin; Hui Zeng; Chao Tan; Jun Wang; Yuguang Zhang; Hai Xing (Cretaceous Research, 2025)

Box-shaped necklace-like Fe3O4/MoS2-CNFs composite nanofibers with confinement effect enhancing sodium storage performance - Huayu Wu; Mohan Yue; Lin He; Miao Zhang; Yimin Huang; Chang Sun; Yu Liu; Jindi Wang; Rongguan Lv; Rong Xing (Chemical Engineering Journal, 2025)

Time-Dependent Transcriptional Dynamics of Contextual Fear Memory Retrieval Reveals the Function of Dipeptidyl Peptidase 9 in Reconsolidation - Wen-Ting Guo; Wen-Xing Li; Yu-Chen Liu; Ya-Bo Zhao; Lin Xu; Qi-Xin Zhou (Neuroscience Bulletin, 2025)
Numerous studies on the formation and consolidation of memory have shown that memory processes are characterized by phase-dependent and dynamic regulation. Memory retrieval, as the only representation of memory content and an active form of memory processing that induces memory reconsolidation, has attracted increasing attention in recent years. Although the molecular mechanisms specific to memory retrieval-induced reconsolidation have been gradually revealed, an understanding of the time-dependent regulatory mechanisms of this process is still lacking. In this study, we applied a transcriptome analysis of memory retrieval at different time points in the recent memory stage. Differential expression analysis and Short Time-series Expression Miner (STEM) depicting temporal gene expression patterns indicated that most differential gene expression occurred at 48 h, and the STEM cluster showing the greatest transcriptional upregulation at 48 h demonstrated the most significant difference. We then screened the differentially-expressed genes associated with that met the expression patterns of those cluster-identified genes that have been reported to be involved in learning and memory processes in addition to dipeptidyl peptidase 9 (DPP9). Further quantitative polymerase chain reaction verification and pharmacological intervention suggested that DPP9 is involved in 48-h fear memory retrieval and viral vector-mediated overexpression of DPP9 countered the 48-h retrieval-induced attenuation of fear memory. Taken together, our findings suggest that temporal gene expression patterns are induced by recent memory retrieval and provide hitherto undocumented evidence of the role of DPP9 in the retrieval-induced reconsolidation of fear memory.

Cross-sectional and Longitudinal Associations Between Metal Mixtures and Serum C3, C4: Result from the Manganese‑exposed Workers Healthy Cohort - Sencai Lin; Junxiu He; Yinghua Zhou; Yu Bao; Xiuming Feng; Hong Cheng; Haiqing Cai; Sihan Hu; Lin Wang; Yuan Zheng; Mengdi Zhang; Qinghua Fan; et al. (Biological Trace Element Research, 2025)

Nonlinear seismic performance of offshore wind turbines on hybrid pile-bucket foundation in sand: Combined earthquake and wind-wave loads - Wei-Yun Chen; Yu-Jie Jiang; Lin-Chong Huang; Ling-Yu Xu; Chao Liu; Guo-Xing Chen (Soil Dynamics and Earthquake Engineering, 2024)

Outdoor light at night is a modifiable environmental factor for metabolic syndrome: The 33 Communities Chinese Health Study (33CCHS) - Li-Wen Hu; Yan-Chen Gong; Hong-Xing Zou; Le-Bing Wang; Yanan Sun; Alejandro Godinez; Han-Yu Yang; Si-Han Wu; Shuo Zhang; Wen-Zhong Huang; Zhao-Huan Gui; Li-Zi Lin; et al. (Science of The Total Environment, 2024)

Observation-based quantification of aerosol transport using optical flow: A satellite perspective to characterize interregional transport of atmospheric pollution - Tianhao Zhang; Yu Gu; Bin Zhao; Lunche Wang; Zhongmin Zhu; Yun Lin; Xing Chang; Xinghui Xia; Zhe Jiang; Hongrong Shi; Wei Gong (Remote Sensing of Environment, 2024)

Comparison of the short- and long-term effects of zinc ions on the anaerobic mesophilic co-digestion of food waste and waste activated sludge: Digester performance, antibiotic resistance gene reduction and the microbial community - Bao-Shan Xing; Yi-Meng Su; Yu-Lin Fu; Yi-Fan Wu; Chen-Hao Yan; Xiaochang C. Wang; Yu-You Li; Rong Chen (Journal of Hazardous Materials, 2024)

Synthesis of cholesterol analogues and comparison on their effect on plasma cholesterol with β-Sitosterol - Hanyue Zhu; Longjian Chen; Zi-Xing Chen; Huiqi Lin; Jianhui Liu; Erika Kwek; Ka Ying Ma; Wensen He; Guoxin Wang; Zhen-Yu Chen (Food Chemistry, 2024)

Transplantation of Wnt5a-modified Bone Marrow Mesenchymal Stem Cells Promotes Recovery After Spinal Cord Injury via the PI3K/AKT Pathway - Haimei Yang; Chaolun Liang; Junhua Luo; Xiuzhen Liu; Wanshun Wang; Kunrui Zheng; Dan Luo; Yu Hou; Da Guo; Dingkun Lin; Xiasheng Zheng; Xing Li (Molecular Neurobiology, 2024)
Spinal cord injury (SCI) is a severe neurological condition that can lead to paralysis or even death. This study explored the potential benefits of bone marrow mesenchymal stem cell (BMSC) transplantation for repairing SCI. BMSCs also differentiate into astrocytes within damaged spinal cord tissues hindering the cell transplantation efficacy, therefore it is crucial to enhance their neuronal differentiation rate to facilitate spinal cord repair. Wnt5a, an upstream protein in the non-classical Wnt signaling pathway, has been implicated in stem cell migration, differentiation, and neurite formation but its role in the neuronal differentiation of BMSCs remains unclear. Thus, this study investigated the role and underlying mechanisms of Wnt5a in promoting neuronal differentiation of BMSCs both in vivo and in vitro. Wnt5a enhanced neuronal differentiation of BMSCs in vitro while reducing astrocyte differentiation. Additionally, high-throughput RNA sequencing revealed a correlation between Wnt5a and phosphoinositide 3-kinase (PI3K)/protein kinase B(AKT) signaling, which was confirmed by the use of the PI3K inhibitor LY294002 to reverse the effects of Wnt5a on BMSC neuronal differentiation. Furthermore, transplantation of Wnt5a-modified BMSCs into SCI rats effectively improved the histomorphology (Hematoxylin and eosin [H&E], Nissl and Luxol Fast Blue [LFB] staining), motor function scores (Footprint test and Basso-Beattie-Bresnahan [BBB]scores)and promoted neuron production, axonal formation, and remodeling of myelin sheaths (microtubule associated protein-2 [MAP-2], growth-associated protein 43 [GAP43], myelin basic protein [MBP]), while reducing astrocyte production (glial fibrillary acidic protein [GFAP]). Therefore, targeting the Wnt5a/PI3K/AKT pathway could enhance BMSC transplantation for SCI treatment.

The effect of paeoniflorin on the rewarding effect of methamphetamine and the associated cognitive impairment in mice - Xin-shuang Gong; Hai-xing Wang; Xiang-dong Yang; Zhao-ying Yu; Shu-jun Lin; Zhi-ting Zou; Jia-nan Lv; Li-yin Qian; Yu-er Ruan; Zi-zhen Si; Yi Zhou; Yu Liu (Metabolic Brain Disease, 2024)

Enhancing effect of conductive materials and rumen microorganisms on the anaerobic digestion performance of a real traditional Chinese medicine wastewater - Han Gao; Xiang-Lin Chang; Su Li; Rong Chen; Yu-You Li; Bao-Shan Xing (Journal of Water Process Engineering, 2024)

Two F-18 radiochemistry methods to synthesize a promising transient receptor potential canonical 5 (TRPC5) radioligand - Yanbo Yu; Sandip B. Jadhav; Zhimin Xing; Hao Jiang; Lin Qiu; Tianyu Huang; Joel S. Perlmutter; Zibo Li; Zhude Tu (Journal of Fluorine Chemistry, 2024)

Electrochemical ratiometric biosensor based on 2D flower-like Co/Ni MOF and sea urchin-like PdCuNi for accurate quantification of alpha-fetoprotein - He-Nan Sun; Miao Wang; Xing-Yu Liu; Lin-Xiao Zhao; Shan-Shan Li (Chemical Engineering Journal, 2024)

Cuproptosis in microsatellite stable colon cancer cells affects the cytotoxicity of CD8+T through the WNT signaling pathway - Jintao Zeng; Hong Chen; Xing Liu; Haoyun Xia; Liqi Chen; Dajia Lin; Naisen Wang; Chong Weng; Guoxian Guan; Yu Zheng (Chemico-Biological Interactions, 2024)

Integrated induction of silver resistance determinants and production of extracellular polymeric substances in Cupriavidus metallidurans BS1 in response to silver ions and silver nanoparticles - Jia-Xin Dai; Yanshuang Yu; Le-Xing You; Hong-Lin Zhong; Yuan-Ping Li; Ai-Jun Wang; Jon Chorover; Ren-Wei Feng; Hend A. Alwathnani; Martin Herzberg; Christopher Rensing (Chemosphere, 2024)

Corrigendum to “In-situ electret scaffolds with controllable electric fields printed by MEW for bone tissue regeneration” [Chem. Eng. J. 496 (2024) 154330] - Xing Zhang; Zhiguang Qiao; Meifei Lian; Yu Han; Jieming Lin; Bin Yu; Linfa Peng; Huamiao Wang; Kerong Dai (Chemical Engineering Journal, 2024)

DEM-CFD coupling simulation and optimisation of rice seed particles seeding a hill in double cavity pneumatic seed metering device - He Xing; Xiaoman Cao; Peng Zhong; Yikai Wan; Junjiang Lin; Yu Zang; Guozhong Zhang (Computers and Electronics in Agriculture, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Association between outdoor light at night exposure and executive function in Chinese children - Han-Yu Yang; Si-Han Wu; Shuo Zhang; Hong-Xing Zou; Le-Bing Wang; Li-Zi Lin; Zhao-Huan Gui; Xiao-Wen Zeng; Bo-Yi Yang; Ru-Qing Liu; Guang-Hui Dong; Li-Wen Hu (Environmental Research, 2024)

In-situ electret scaffolds with controllable electric fields printed by MEW for bone tissue regeneration - Xing Zhang; Zhiguang Qiao; Meifei Lian; Yu Han; Jieming Lin; Bin Yu; Linfa Peng; Huamiao Wang; Kerong Dai (Chemical Engineering Journal, 2024)

Boronate-modified electro-spun Fe doped carbon nanofibrous membrane for selective dye adsorption, catalytic degradation, and bacterial inhibition in treatment of water - De-yu Tang; Ling-ling Yan; Luo-lin Deng; Xing-han Wang; Ya-li Xiang; Qing-li Li; Juan Lin; Qing-han Zhou (Chemical Engineering Journal, 2024)

Pichia pastoris composition expressed aerolysin mutant of Aeromonas veronii as an oral vaccine evaluated in zebrafish (Danio rerio) - Yuan-Yuan Yao; Qing-Shuang Zhang; Shu-Bin Liu; Hong-Wei Yang; Xing-Yu Chen; Ya-Lin Yang; Chen-Chen Gao; Chao Ran; Tsegay Teame; Zhen Zhang; Zhi-Gang Zhou (Marine Life Science & Technology, 2024)
Vaccines are one of the most practical means to stop the spreading of Aeromonas veronii in aquaculture. In this study, virulence factor aerolysin mutant NTaer which has lost its hemolytic activity was used as a target antigen. Pichia pastoris constitutive secretory expression NTaer (GS115-NTaer) was used as a potential safe oral vaccine to evaluate its effectiveness on zebrafish immunity. The result shows that vaccination of GS115- NTaer for four weeks did not affect the growth performance of the host, while eliciting an effective immune protective response. Compared with the control group, the GS115-NTaer could significantly up-regulate the relative expression level of the intestinal tight junction protein 1α ( TJP1α ) gene, and significantly increased the contents of lysozyme (LYZ), complement C3 and C4 in the gut, indicating that the innate immune response of the fish was activated. The relative gene expression levels of macrophage-expressed gene 1 ( MPEG1 ) and T cell receptor ( TCR-α ) in the gut, and MPEG1 , CD4 , CD8 , TCR-α , GATA3, and T-bet in the spleen were all increased significantly, indicating that the cellular immune response of the fish was activated. Furthermore, the contents of serum IgM and intestinal mucosa IgZ antibodies were significantly increased, which showed that humoral immunity was also activated. Moreover, inoculation with GS115-NTaer significantly changed the structure of gut microbiota. In particular, the relative ratio of (Firmicutes + Fusobacteriota + Bacteroidota)/Proteobacteria was significantly higher than that of the control and GS115 groups. Lastly, the vaccinated fish were challenged with A. veronii, and the relative percent survival of GS115 and the GS115-NTear groups was 14.28% and 33.43%. This improvement of immunity was not only due to the specific immune response but also attributed to the improvement of innate immunity and the gut microbiota which was demonstrated by the germ-free zebrafish model. Collectively, this study provides information on the effectiveness of GS115-NTear as an oral vaccine for the green prevention and control of A. veronii infection in fish aquaculture.

Behavioral events and functional analysis of bursicon signal during adult eclosion in the 28-spotted larger potato ladybird - Wen-Ze Li; Yi-Kuan Wu; Yu-Xing Zhang; Lin Jin; Guo-Qing Li (Pesticide Biochemistry and Physiology, 2024)

Energy-economy-environment assessment of key feedstock production for ternary lithium-ion batteries via hydrometallurgical recycling and natural exploitation - Kai Wang; Quanshui Huang; Ran Feng; Shaojun Liu; Peng Xing; Zi-Tao Yu; Qingyang Lin; Xiang Gao (Journal of Cleaner Production, 2024)

In vivo study on osteogenic efficiency of nHA/ gel porous scaffold with nacre water-soluble matrix - SiRi-GuLeng Li; Zhu-Ling Guo; Si-Yu Tao; Tao Han; Jie Zhou; Wan-Yun Lin; Xiang Guo; Chu-Xing Li; Sunchuri Diwas; Xiao-Wen Hu (Tissue and Cell, 2024)

Anti-pancreatic cancer activity of cassane diterpenoids isolated from the seeds of Caesalpinia sappan mediated by autophagy activation via ROS/AMPK/mTORC1 pathway - Jia Su; De-Sheng Wang; Guo-Xian Hu; Yu-Yao Liu; Ming Hu; Ya Chen; Qi-Qi Wang; Run-Cheng Yan; Yun Wu; Yong-Jiao Li; Ke Ma; Yan-Yan Qi; et al. (Phytochemistry, 2024)

A compound enzyme as an additive to a continuous anaerobic dynamic membrane bioreactor for enhanced lignocellulose removal from codigestion: Performance, membrane characteristics and microorganisms - Bao-Shan Xing; Xiang-Lin Chang; Yi Zhang; Sifan Cao; Xi-Fang Tang; Yong-Chen Han; Yu-You Li; Xiaochang C. Wang; Rong Chen (Bioresource Technology, 2024)

Therapeutic effects and mechanisms of isoxanthohumol on DSS-induced colitis: regulating T cell development, restoring gut microbiota, and improving metabolic disorders - Ya-Na Yang; Bing Han; Mao-Qing Zhang; Na-Nan Chai; Feng-Lin Yu; Wen-Hui Qi; Meng-Yuan Tian; Dong-Zhi Sun; Ying Huang; Qing-Xin Song; Yan Li; Mao-Cui Zhu; et al. (Inflammopharmacology, 2024)

Comprehensive effects of microplastics on algae-laden surface water treatment by coagulation-ultrafiltration combined process: Algae cultivation, coagulation performance and membrane fouling development - Dachao Lin; Zhongjian Zhuang; Nan Yu; Zhihong Wang; Wei Song; Xing Du (Science of The Total Environment, 2024)

Nanozyme sensor array based on Fe, Se co-doped carbon material for the discrimination of Sulfur-containing compounds - Enxiang Ren; Haochen Qiu; Zhixuan Yu; Min Cao; Muhammad Sohail; Guo-Ping Lu; Xing Zhang; Yamei Lin (Journal of Hazardous Materials, 2024)

Hepatic injury and ileitis associated with gut microbiota dysbiosis in mice upon F–53B exposure - Shenpan Li; LuYin Wu; HuiXian Zeng; Jing Zhang; ShuangJian Qin; Li-Xia Liang; John Andersson; Wen-Jie Meng; Xing-Yu Chen; Qi-Zhen Wu; Li-Zi Lin; Wei-Chun Chou; et al. (Environmental Research, 2024)

Multifunctional triboelectric nanogenerator for wind energy harvesting and mist catching - Fei Zhang; Lin Zheng; Hao Li; Gao Yu; Shengbo Wang; Fangjing Xing; Zhong Lin Wang; Baodong Chen (Chemical Engineering Journal, 2024)

Bio-based and fireproof radiative cooling aerogel film: Achieving higher sustainability and safety - Wei Cai; Bicheng Lin; Liangyuan Qi; Tianyang Cui; Zhaoxin Li; Junling Wang; Sicheng Li; Chengfei Cao; Mohammad Ziaur Rahman; Xin Hu; Rujun Yu; Shuo Shi; et al. (Chemical Engineering Journal, 2024)

A new substrate equalization method for optimizing the influent conditions and fluid flow patterns of a multifed upflow anaerobic sludge blanket reactor with mature anammox granules - Bao-Shan Xing; Xi-Fang Tang; Ling-Hu Li; Yu-Lin Fu; Jia-Yi Liu; Ya-Ge Wang; Xin-Xin Sun; Yu-You Li; Rong Chen; Ren-Cun Jin (Bioresource Technology, 2024)

PdPtVO /CeO2−ZrO2: Highly efficient catalysts with good sulfur dioxide-poisoning reversibility for the oxidative removal of ethylbenzene - Jia Wang; Yuxi Liu; Jiguang Deng; Lin Jing; Xiuqing Hao; Xing Zhang; Xiaohui Yu; Hongxing Dai (Journal of Environmental Sciences, 2024)

Transplantation of MiR-28-5p-Modified BMSCs Promotes Functional Recovery After Spinal Cord Injury - Zhen Li; Haitao Su; Guandai Lin; Kai Wang; Yongming Huang; Yaqian Wen; Dan Luo; Yu Hou; Xuewei Cao; Jiaxian Weng; Dingkun Lin; Le Wang; et al. (Molecular Neurobiology, 2024)
Traumatic spinal cord injury (TSCI) is a prevalent central nervous system condition that imposes a significant burden on both families and society, affecting more than 2 million people worldwide. Recently, there has been increasing interest in bone marrow mesenchymal stem cell (BMSC) transplantation as a promising treatment for spinal cord injury (SCI) due to their accessibility and low immunogenicity. However, the mere transplantation of BMSCs has limited capacity to directly participate in the repair of host spinal cord nerve function. MiR-28-5p, identified as a key differentially expressed miRNA in spinal cord ischemia–reperfusion injury, exhibits differential expression and regulation in various neurological diseases. Nevertheless, its involvement in this process and its specific regulatory mechanisms in SCI remain unclear. Therefore, this study aimed to investigate the potential mechanisms through which miR-28-5p promotes the neuronal differentiation of BMSCs both in vivo and in vitro. Our results indicate that miR-28-5p may directly target Notch1, thereby facilitating the neuronal differentiation of BMSCs in vitro . Furthermore, the transplantation of lentivirus-mediated miR-28-5p-overexpressed BMSCs into SCI rats effectively improved footprint tests and Basso, Beattie, and Bresnahan (BBB) scores, ameliorated histological morphology (hematoxylin–eosin [HE] and Nissl staining), promoted axonal regeneration (MAP2 and growth-associated protein 43 [GAP43]), and facilitated axonal remyelination (myelin basic protein [MBP]). These findings may suggest that miR-28-5p-modified BMSCs could serve as a therapeutic target to enhance the behavioral and neurological recovery of SCI rats.

Migration of phosphorus in pig manure during pyrolysis process and slow-release mechanism of biochar in hydroponic application - Ru-Qing Jiang; Guang-Wei Yu; Lin-Hui Yu; Yu Wang; Chang-Jiang Li; Zhen-Jiao Xing; Xi-Mei Xue; Yin Wang; Cheng Yu (Science of The Total Environment, 2024)

Enhanced electrooxidation/electrocoagulation-ultrafiltration membrane process with S2O42− for saline algae-containing surface water treatment: Purification and membrane performance - Wei Song; Bingxuan Li; Zhongjian Zhuang; Xing Du; Dachao Lin; Yu Zhou; Zhihong Wang (Environmental Pollution, 2024)

Electropolymerization stabilized bipolar metal coordination complex for high-performance dual-ion batteries - Chen-xing Zhang; Xian-he Chen; Wei-sheng Zhang; Yue Wang; Shi-lin Mei; Yu-Wu Zhong; Chang-Jiang Yao (Chemical Engineering Journal, 2024)

Thermally managed and fireproof composite aerogels for safer and year-round energy saving - Wei Cai; Zhaoxin Li; Heng Xie; Wei Wang; Tianyang Cui; Bicheng Lin; Liangyuan Qi; Xin Hu; Yu Du; Yang Ming; Shuo Shi; Daming Chen; et al. (Chemical Engineering Journal, 2024)

Large-n quasi-phase-pure two-dimensional halide perovskite: A toolbox from materials to devices - Zijia Li; Yuexin Lin; Hao Gu; Nan Zhang; Bin Wang; Hairui Cai; Jinfeng Liao; Dejian Yu; Yiwang Chen; Guojia Fang; Chao Liang; Shengchun Yang; et al. (Science Bulletin, 2024)

Enhanced organic matter humification by hydroxyl radical generation during electric field-assisted aerobic composting - Ruizhi Xing; Keke Yin; Xian Du; Ying Lin; Zhen Yu; Zhi Chen; Shungui Zhou (Chemical Engineering Journal, 2024)

Peroxisome Proliferator-Activated Receptor-γ Coactivator-1α in the Spotlight with Multiple Sclerosis - Ya-Na Yang; Mao-Qing Zhang; Feng-Lin Yu; Bing Han; Ming-Yue Bao; Yan He; Xing Li; Yuan Zhang (Neuroscience Bulletin, 2024)

Eudesmane-type sesquiterpenoids from the aerial parts of Artemisia lavandulaefolia and their anti-pancreatic cancer activities - Lin-Fen Ding; Guo-Xian Hu; Yu-Yao Liu; Qiu-Hua Wang; Zhang-Juan Li; Meng-Xia Shen; Gui-Fa Zhu; Xing-De Wu; Jia Su (Phytochemistry, 2023)

CNT-based water-induced generator for effective self-powered devices via superior synergism between electrokinetic and galvanic effects - Linan Xu; Wenxing Wang; Xiaoguang Li; Hongjian Yu; Xinyuan Liu; Yang Zhang; Hongyang Xu; Song Lin; Xing Yi Ling; Haitao Li (Chemical Engineering Journal, 2023)

CDK6 is a novel predictive and prognosis biomarker correlated with immune infiltrates in multiple human neoplasms, including small cell lung carcinoma - Guo-Sheng Li; Zhi-Guang Huang; Dong-Ming Li; Yu-Lu Tang; Jin-Hua Zheng; Lin Yang; Yue Feng; Jun-Xi Peng; Jing-Xiao Li; Yu-Xing Tang; Neng-Yong Zeng; Mei-Hua Jin; et al. (Functional & Integrative Genomics, 2023)

Comparison of demineralized bone matrix with different cycling crushing times in posterolateral fusion model of athymic rats - Shao-Lin Ji; Xiao-Dan Zhao; Li-Min Wang; Cheng-Gang Pang; Wen-Jing Li; Kun-Xiu Song; Rong-Xing Ma; Rui-Feng Li; Jing-Yu Zhang; Yong-Cheng Hu (Cell and Tissue Banking, 2023)

Prediction of cadmium contents in rice grains from Quaternary sediment-distributed farmland using field investigations and machine learning - Xudong Ma; Tao Yu; Dong-Xing Guan; Cheng Li; Bo Li; Xu Liu; Kun Lin; Xuezhen Li; Lei Wang; Zhongfang Yang (Science of The Total Environment, 2023)

Scene-aware refinement network for unsupervised monocular depth estimation in ultra-low altitude oblique photography of UAV - Kailong Yu; Hao Li; Linjie Xing; Tao Wen; Die Fu; Yang Yang; Chengjiang Zhou; Rong Chang; Shan Zhao; Lin Xing; Haicheng Bai (ISPRS Journal of Photogrammetry and Remote Sensing, 2023)

3D printing of customizable and lightweight multilayer MXene/nanocellulose architectures for tunable electromagnetic interference shielding via direct ink writing - Lei Chen; Tian Mai; Xing-Xiang Ji; Pei-Lin Wang; Meng-Yu Qi; Qi Liu; Yan Ding; Ming-Guo Ma (Chemical Engineering Journal, 2023)

Design, synthesis, and biological activity of 9- O -cinnamoylberberines as novel lipid-lowering agents - Yuan Kong; Qi-Qi Xing; Yu-Xuan Tian; Lin Li; Pan Yu; Lin-Guo Zhao; Dong-Dong Li (Natural Product Research, 2023)

Chemical constituents from the leaves of Cinnamomum camphora and their α-glucosidase inhibitory activities - Xing Jiang; Xi-Han Zhang; Yu-Xin Li; Kai Chen; Bin Lin; Tian-Qi Lu; Min Yang; Guang-Tong Chen; Bo-Yi Fan; Wen-Li Wang (Phytochemistry Letters, 2023)

Host-derived peptide signals regulate Pseudomonas aeruginosa virulence stress via the ParRS and CprRS two-component systems - Ning-Lin Zhao; Zi-Qi Zhu; Han-Zhong Feng; Ying-Jie Song; Qin Huang; Xing-Yu Mou; Cheng Nong; Yong-Xing He; Rui Bao (Journal of Hazardous Materials, 2023)

The shear resistance mechanism of prestressed anchor cables in slope reinforcement - Xiao-Gang Wang; Yu-Fei Zhao; Yong Nie; Xing-Chao Lin; Xing-Song Sun (International Journal of Rock Mechanics and Mining Sciences, 2023)

A modified Newmark block method for determining the seismic displacement of a slope reinforced by prestressed anchors - Li Lu; Yu-Liang Lin; Dong-Dong Guo; Hao Xing; Zhen Zhang; Jun-Yi Duan (Computers and Geotechnics, 2023)

Dynamic pore modulation of contracted carbon fiber filter for wastewater treatment: Filtration performance and in-situ regeneration mechanism - Tao Xu; Lin Shi; Senlin Shao; Hui Wang; Yu Huang; Lei Xing; Re Xia; Ruggero Rossi; Liandong Zhu; Hua Zhu; Wulin Yang; Xuhui Mao; et al. (Chemical Engineering Journal, 2023)

GABAergic Neurons in the Nucleus Accumbens are Involved in the General Anesthesia Effect of Propofol - Jing Yan; Bei-Ning Hang; Lin-Hui Ma; Jia-Tao Lin; Yue Zhou; Xin-Hao Jiao; Ying-Xuan Yuan; Ke-Jie Shao; Le-Meng Zhang; Qi Xue; Zi-Yi Li; Hong-Xing Zhang; et al. (Molecular Neurobiology, 2023)

Research on stability and control strategies for a spring-loaded valve with bypass outlet - Jie Jian; Zhi-Jun Shuai; Jia-Xuan He; Chang-Lin Meng; Tao Yu; Xi Wang; Wan-You Li; Shi-Wei Ni; Chen-Xing Jiang (Annals of Nuclear Energy, 2023)

Revealing the solid-solution interface interference behaviors between Cu2+ and As(III) via partial peak area analysis of simulations and experiments - Bo Liang; Xiang-Yu Xiao; Zong-Yin Song; Yong-Yu Li; Xin Cai; Rui-Ze Xia; Shi-Hua Chen; Meng Yang; Pei-Hua Li; Chu-Hong Lin; Xing-Jiu Huang (Analytica Chimica Acta, 2023)

Associations of metal mixtures with thyroid function and potential interactions with iodine status: results from a cross-sectional study in MEWHC - Xiaoting Ge; Junxiu He; Sencai Lin; Yu Bao; Yuan Zheng; Hong Cheng; Haiqing Cai; Xiuming Feng; Wenjun Yang; Sihan Hu; Lin Wang; Qijing Liao; et al. (Environmental Science and Pollution Research, 2023)

Metformin improves sheep sperm cryopreservation via vitalizing the AMPK pathway - Xing Zhang; Song-Mao Guo; Da-Wei Zhu; Yu Li; Fei Wen; Ming Xian; Zhang-Tao Hu; Qian-Long Zou; Li-Kun Zhang; Yu-Lin Chen; Jian-Hong Hu (Theriogenology, 2023)

Metabolomic profiling of Panax ginseng in response to Fusarium solani infection - Guijia Zhao; Shuyang Xing; Yang Wang; Xu Yang; Ru Sun; Lin Feng; Jifeng Wang; Tianxia Sun; Wenhui Lian; Yu Zhao (Physiological and Molecular Plant Pathology, 2023)

Short-term operation optimization for natural gas pipeline considering line-pack: A perspective of optimal transport - Chongyuan Shui; Dengji Zhou; Zheng Wu; Weichao Yu; Lin Zhang; Tongsheng Xing; Chen Wang; Zhaonan Du (Gas Science and Engineering, 2023)

An anaerobic dynamic membrane bioreactor (AnDMBR) system enhanced the biogas conversion efficiency and stability of mesophilic codigestion with waste activated sludge and food waste - Bao-Shan Xing; Yi Zhang; Rui-Qi Zhang; Jing Ma; Xiang-Lin Chang; Xi-Fang Tang; Yu-You Li; Xiaochang C. Wang; Rong Chen (Chemical Engineering Journal, 2023)

Association of mitochondrial DNA variation with high myopia in a Han Chinese population - Shilai Xing; Siyi Jiang; Siyu Wang; Peng Lin; Haojun Sun; Hui Peng; Jiaying Yang; Hengte Kong; Sheng Wang; Qingshi Bai; Ruowen Qiu; Wei Dai; et al. (Molecular Genetics and Genomics, 2023)
High myopia (HM), which is characterized by oxidative stress, is one of the leading causes of visual impairment and blindness across the world. Family and population genetic studies have uncovered nuclear-genome variants in proteins functioned in the mitochondria. However, whether mitochondrial DNA mutations are involved in HM remains unexplored. Here, we performed the first large-scale whole-mitochondrial genome study in 9613 HM cases and 9606 control subjects of Han Chinese ancestry for identifying HM-associated mitochondrial variants. The single-variant association analysis identified nine novel genetic variants associated with HM reaching the entire mitochondrial wide significance level, including rs370378529 in ND2 with an odds ratio (OR) of 5.25. Interestingly, eight out of nine variants were predominantly located in related sub-haplogroups, i.e. m.5261G > A in B4b1c, m.12280A > G in G2a4, m.7912G > A in D4a3b, m.94G > A in D4e1, m.14857 T > C in D4e3, m.14280A > G in D5a2, m.16272A > G in G2a4, m.8718A > G in M71 and F1a3, indicating that the sub-haplogroup background can increase the susceptible risk for high myopia. The polygenic risk score analysis of the target and validation cohorts indicated a high accuracy for predicting HM with mtDNA variants (AUC = 0.641). Cumulatively, our findings highlight the critical roles of mitochondrial variants in untangling the genetic etiology of HM.

Ratiometric SERS imaging for indication of peroxynitrite fluctuations in diabetic wound healing process - Hui Chen; Shanshan Lin; Dianqi Zhang; Yanlong Xing; Fabiao Yu; Rui Wang (Chemical Engineering Journal, 2023)

Long-term in-situ starvation and reactivation of co-digestion with food waste and corn straw in a continuous AnDMBR: Performance, sludge characteristics, and microorganism community - Bao-Shan Xing; Xiang-Lin Chang; Sifan Cao; Dong Wu; Yi Zhang; Xi-Fang Tang; Yu-You Li; Xiaochang C. Wang; Rong Chen (Science of The Total Environment, 2023)

Design, Synthesis and Herbicidal Evaluation of Novel Urea Derivatives with Inhibition Activity to Root Growth - Lin Du; Zhikun Yang; Huiqi Zhang; Keke Yu; Xing Wang; Weiming Tan; Liusheng Duan (Journal of Plant Growth Regulation, 2023)

U-shaped association between low-density lipoprotein cholesterol levels and risk of all-cause mortality mediated by post-stroke infection in acute ischemic stroke - Zi-Mo Chen; Hong-Qiu Gu; Jing-Lin Mo; Kai-Xuan Yang; Ying-Yu Jiang; Xin Yang; Chun-Juan Wang; Jie Xu; Xia Meng; Yong Jiang; Hao Li; Li-Ping Liu; et al. (Science Bulletin, 2023)

New dimeric sesquiterpenoids from the whole plant of Artemisia sieversiana - Jun-yi Dong; Yu-xing Cai; Ya-lin Li; Yu-xin Zhang; Zhan-peng Yu; Ling-yi Kong; Jian-guang Luo (Phytochemistry Letters, 2023)

Numerical study on unsteady propeller exciting characteristics considering shafting whirling vibration effect - Chang-Lin Meng; Zhi-Jun Shuai; Tao Yu; Ke-Xin Ren; Jie Jian; Xi Wang; Dong-Hua Wang; Wan-You Li; Chen-Xing Jiang (Ocean Engineering, 2023)

Cues of intraguild predators (Harmonia axyridis) and different temperatures alter foraging and oviposition strategies of the parasitoid Aphidius gifuensis - Xing-Lin Yu; Yi Feng; Tong-Xian Liu; Bao-Li Qiu (Journal of Asia-Pacific Entomology, 2023)

Synergistic effect of intercalation and EDLC electrosorption of 2D/3D interconnected architectures to boost capacitive deionization for water desalination via MoSe2/mesoporous carbon hollow spheres - Jiaxin Du; Wenle Xing; Jiaqi Yu; Jing Feng; Lin Tang; Wangwang Tang (Water Research, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Magnetic ternary layered double hydroxides for efficient removal of 1-naphthalene acetic acid from waters: Adsorption behavior and mechanism - Ti-Bo Fang; Hua Xiao; Ling-Xi Zhao; Na Li; Ling-Yu Luan; Zhao-Xing Yan; Jin-Ming Lin; Ru-Song Zhao (Journal of Environmental Chemical Engineering, 2023)

The positive effects of postbiotic (SWF concentration®) supplemented diet on skin mucus, liver, gut health, the structure and function of gut microbiota of common carp (Cyprinus carpio) fed with high-fat diet - Zhe Yu; Qiang Hao; Shu-Bin Liu; Qing-Shuang Zhang; Xing-Yu Chen; Sheng-Hui Li; Chao Ran; Ya-Lin Yang; Tsegay Teame; Zhen Zhang; Zhi-Gang Zhou (Fish & Shellfish Immunology, 2023)

Click-crosslinked in-situ hydrogel improves the therapeutic effect in wound infections through antibacterial, antioxidant and anti-inflammatory activities - Xiong-Xin Lei; Chen-Yu Zou; Juan-Juan Hu; Yan-Lin Jiang; Xiu-Zhen Zhang; Long-Mei Zhao; Tao He; Qing-Yi Zhang; Ya-Xing Li; Jesse Li-Ling; Hui-Qi Xie (Chemical Engineering Journal, 2023)

Interaction Between the Glymphatic System and α-Synuclein in Parkinson’s Disease - Yu Zhang; Cui Zhang; Xu-Zhong He; Zhen-Hua Li; Jing-Cai Meng; Rui-Ting Mao; Xin Li; Rong Xue; Qian Gui; Guo-Xing Zhang; Lin-Hui Wang (Molecular Neurobiology, 2023)

Diverse alkaloids from the aerial parts of Aconitum carmichaelii and antiproliferative activity of costemline via inhibiting SIRT1/ROCK1/P-STAT3 pathways - Yin-Lin Zhou; Duan-Na Zhang; Ji-Xu Qiao; Jing Wu; Yong-Ming Yan; Zhi-Xing Cao; Cheng Peng; Yu-Zhu Tan (Phytochemistry, 2023)

Rising temperatures affect the interspecific interference competition between Harmonia axyridis and Propylea japonica, and their predation rate on Myzus persicae - Xing-Lin Yu; Yu-Jie Zhang; Jun-Feng Zuo; Xun Luo; Long Zhang; Zhuo-Ma Danzeng; Bo Wang; Peng-Liang Xia; Shi-Ze Zhang; Tong-Xian Liu; Yi Feng (Journal of Pest Science, 2023)

Dynamic changes in cell wall-degrading enzymes and physio-biochemistry of ginseng in response to fusarium oxysporum infection - Lin Feng; Guijia Zhao; Ru Sun; Jifeng Wang; Tianxia Sun; Shuyang Xing; Wenhui Lian; Yu Zhao (European Journal of Plant Pathology, 2023)

Effects of demineralization mode and particle size of allogeneic bone powder on its physical and chemical properties - Kun-xiu Song; Shao-lin Ji; Yong-jie Zhao; Hao-ran Zhang; Rong-xing Ma; Jing-yu Zhang; Yong-cheng Hu (Cell and Tissue Banking, 2023)

ARSCP: An antimicrobial residue surveillance cloud platform for animal-derived foods - Jun-Jun Yu; Ya-Lin Hu; Cheng-Zheng Liu; Shuai-Bin Wu; Zi-Jian Zheng; Ze-Hua Cui; Li Chen; Tian Wei; Shi-Kai Sun; Jun Ning; Xiang Wen; Qiu-Yue Diao; et al. (Science of The Total Environment, 2023)

The construction of high efficient visible-light-driven 3D porous g-C3N4/Fe3O4 photocatalyst: A new photo-induced bacterial inactivation material enhanced by cascade photo-Fenton reaction - Ze-Yu Liu; Wen-Qian Huang; Chuan-Qing Huang; Zhao-Zhen Liu; Xiao-Yue Tang; Wei-Chang Chen; Zheng-Zheng Tang; Yu-Xing Huang; Shuo-Chun Zheng; Lin Lin; Changzhu Li; Yong Ye (Chemosphere, 2023)

Insight into the Co2+/Co3+ sites for the selective reduction of furfural to furfuryl alcohol - Jiahong Chen; Wenlong Jia; Xin Yu; Yong Sun; Jiaren Zhang; Shuliang Yang; Xing Tang; Lincai Peng; Xianhai Zeng; Lu Lin (Fuel, 2023)

Inheritance and Development: The Evolution and Overview of China’s Fisheries Legal System - Wei Wu; Yang Liu; Zhaobin Pei; Yan Lin; Xin Sun; Jiaqi Xing; Yuwei Wang; Yu Liu (Fishes, 2022)
China’s legal system governing fisheries in China has been stable during development. In line with China’s national conditions and the spirit of the times, they have adhered to the concept of green development and maintaining the sustainable development of fishery production activities. Studying the history of Chinese fishery law is beneficial for the world to understand the evolution of this legislation and is a better gateway for the world to understand fisheries law with Chinese characteristics. Fishery, in this context, refers to fishing and fish farming. In China, fisheries are under the management of the Ministry of Agriculture and Rural Affairs, while fisheries enforcement has a special law enforcement department for collaborative management. Therefore, both fishing and fish farming in China’s fisheries industry belong to the category of agriculture. This is different from the West and is precisely what makes China unique. This paper explores the Chinese fishery legal and general legal systems by investigating policy guidelines, laws, and regulations on China’s fishery industry since 1949. Furthermore, it analyzes the development process of fisheries. Organizing the development status of China’s fishery legal and regulatory system analyzes the problems of fishery production control and development, searches for paths and methods to solve the practical problems, and finally, makes a reasonable outlook on the development prospect of China’s fishery.

Regulation of enzymatic and non-enzymatic antioxidants in rice seedlings against chromium stress through sodium hydrosulfide and sodium nitroprusside - Yu-Juan Lin; Xing-Hui Feng; Yu-Xi Feng (Environmental Science and Pollution Research, 2022)

NAD+-capped RNAs are widespread in rice (Oryza sativa) and spatiotemporally modulated during development - Haijiao Dong; Xufeng Wang; Cong Tan; Lei Gao; Jie Cui; Lin Liu; Beixin Mo; Yongzhong Xing; Yu Yu; Xuemei Chen (Science China Life Sciences, 2022)

Validity Analysis of the Morphological Identification of Three Highly Morphologically Similar Species Belonging to the Genus Niviventer (Rodentia: Muridae) - Yao-Yao Li; Hao-Tian Li; Jia-Wei Hao; Chen-Yi Zhang; Guan-Ze Liu; Xing-Han Lin; Xiao-Qing Sun; Guo-Chen Zang; Yu-Chun Li (Journal of Mammalian Evolution, 2022)

Correction to: Matrine Treatment Blocks NogoA-Induced Neural Inhibitory Signaling Pathway in Ongoing Experimental Autoimmune Encephalomyelitis - Quan-Cheng Kan; Hui-Jun Zhang; Yuan Zhang; Xing Li; Yu-Ming Xu; Rodolfo Thome; Ming-Liang Zhang; Nan Liu; Yao-Juan Chu; Guang-Xian Zhang; Lin Zhu (Molecular Neurobiology, 2022)

Identification and expression profiling of HSP20 genes in Neoporphyra haitanensis - Ling-Na Peng; Lin-Bin Huang; Tian-Yu Gui; Da-Hai Gao; Xing-Hong Yan (Journal of Applied Phycology, 2022)

Characterization of alkaloids in radix Sophora tonkinensis by UPLC-Q-TOF-MS/MS and its application in the comparison of two different habitats - Xing-Xing Zong; Yu Wang; Jia-Liang Xiong; Yu-Hui Ping; Qiong-Lin Liang (Natural Product Research, 2022)

Temporal stability analysis of soil moisture along a coniferous forest hillslope with subtropical monsoon climate in southwest China - Yu-shi Bai; Mu-xing Liu; Jun Yi; Hai-lin Zhang (Journal of Mountain Science, 2021)

Anti-miR33 therapy improved hepatopancreatic lipid and immune metabolism disorders in grass carp, Ctenopharyngodon idella - Rong-Hua Lu; Meng-Jun Lin; Feng Yang; Shen-zong Jia; Yu-Ru Zhang; Chao-Bin Qin; Xiao-Lin Meng; Guo-Xing Nie (Fish Physiology and Biochemistry, 2021)

Plant multiscale networks: charting plant connectivity by multi-level analysis and imaging techniques - Xi Zhang; Yi Man; Xiaohong Zhuang; Jinbo Shen; Yi Zhang; Yaning Cui; Meng Yu; Jingjing Xing; Guangchao Wang; Na Lian; Zijian Hu; Lingyu Ma; et al. (Science China Life Sciences, 2021)

Cytotoxic p -terphenyls from the deep-sea-derived Aspergillus candidus - Yu-Kun Lin; Chun-Lan Xie; Cui-Ping Xing; Bao-Qu Wang; Xiao-Xue Tian; Jin-Mei Xia; Ling-Yun Jia; Ying-Ni Pan; Xian-Wen Yang (Natural Product Research, 2021)

Exposed to Mercury-Induced Oxidative Stress, Changes of Intestinal Microflora, and Association between them in Mice - Yulan Zhao; Changming Zhou; Xiaoquan Guo; Guoliang Hu; Guyue Li; Yu Zhuang; Huabin Cao; Lin Li; Chonghong Xing; Caiying Zhang; Fan Yang; Ping Liu (Biological Trace Element Research, 2021)

Cryostructures and ground ice content in ice-rich permafrost area of the Qinghai-Tibet Plateau with Computed Tomography Scanning - Xing-wen Fan; Zhan-ju Lin; Ze-yong Gao; Xiang-lian Meng; Fu-jun Niu; Jing Luo; Guo-an Yin; Fu-jun Zhou; Ai-yu Lan (Journal of Mountain Science, 2021)

Mortality burden caused by diurnal temperature range: a nationwide time-series study in 364 Chinese locations - Min Cai; Jianxiong Hu; Chunliang Zhou; Zhulin Hou; Yanjun Xu; Maigeng Zhou; Yize Xiao; Biao Huang; Xiaojun Xu; Lifeng Lin; Tao Liu; Jianpeng Xiao; et al. (Stochastic Environmental Research and Risk Assessment, 2021)

Adaptive Evolution of Chalcone Isomerase Superfamily in Fagaceae - Li-Mei Lin; Hong-Yu Guo; Xin Song; Duo-Duo Zhang; Yue-Hong Long; Zhao-Bin Xing (Biochemical Genetics, 2021)

At3g53630 encodes a GUN1-interacting protein under norflurazon treatment - Xing-Qi Huang; Lin-Juan Wang; Meng-Juan Kong; Na Huang; Xin-Ya Liu; Han-Yu Liang; Jia-Xin Zhang; Shan Lu (Protoplasma, 2021)

Effects of degradation succession of alpine wetland on soil organic carbon and total nitrogen in the Yellow River source zone, west China - Chun-ying Lin; Xi-lai Li; Jing Zhang; Hua-fang Sun; Juan Zhang; Hui-bang Han; Qi-hua Wang; Cheng-biao Ma; Cheng-yi Li; Yu-xing Zhang; Xue-qian Ma (Journal of Mountain Science, 2021)

Roles of FERONIA-like receptor genes in regulating grain size and quality in rice - Long Wang; Dandan Wang; Zhuhong Yang; Shun Jiang; Jianing Qu; Wei He; Zhenming Liu; Junjie Xing; Youchu Ma; Qinlu Lin; Feng Yu (Science China Life Sciences, 2021)

First report of turnip mosaic virus on yellow passion fruit in China - Li Juan Chen; Xing Xing Zhang; Ying Lin Lu; Yu Xing An (Journal of Plant Pathology, 2021)

A plant virus mediates interspecific competition between its insect vectors in Capsicuum annuum - Yong Chen; Xue Zheng; Hui Wei; Yong-Dui Chen; Kuan-Yu Zheng; Ye Mu; Xing-Yue Zhao; Li-Hua Zhao; Yu-Lin Gao; Li-Min Zheng; Jie Zhang (Journal of Pest Science, 2021)

Quantitative Determination of Glymphatic Flow Using Spectrophotofluorometry - Yu Zhang; Jian Song; Xu-Zhong He; Jian Xiong; Rong Xue; Jia-Hao Ge; Shi-Yu Lu; Die Hu; Guo-Xing Zhang; Guang-Yin Xu; Lin-Hui Wang (Neuroscience Bulletin, 2020)

First report of ramie mosaic virus on passion fruit in Guangdong, southern China - Li Juan Chen; Dong Lei Sun; Ying Lin Lu; Yu Xing An (Journal of Plant Pathology, 2020)

Transcriptional analysis reveals physiological response to acute acidification stress of barramundi Lates calcarifer (Bloch) in coastal areas - Zhenhua Ma; Xing Zheng; Zhengyi Fu; Siqi Lin; Gang Yu; Jian G. Qin (Fish Physiology and Biochemistry, 2020)

Grape seed proanthocyanidin extract ameliorates hepatic lipid accumulation and inflammation in grass carp (Ctenopharyngodon idella) - Rong-Hua Lu; Chao-Bin Qin; Feng Yang; Wen-Ya Zhang; Yu-Ru Zhang; Guo-Kun Yang; Li-Ping Yang; Xiao-Lin Meng; Xiao Yan; Guo-Xing Nie (Fish Physiology and Biochemistry, 2020)

2D slope stability analysis based on Pan’s maximum principle - Xiao Gang Wang; Xing Chao Lin; Ping Sun; Xu Li; Yu Jie Wang; Yong Yu Ling (Bulletin of Engineering Geology and the Environment, 2020)

Novel dammarane-type saponins from Gynostemma pentaphyllum and their neuroprotective effect - Shao-Fang Xing; Man Lin; Yu-Rong Wang; Tuo Chang; Wei-Ye Cui; Xiang-Lan Piao (Natural Product Research, 2020)

Effect of slope gradient on the subsurface water flow velocity of sand layer profile - Zhen Han; Xiao-yan Chen; Yu-han Huang; Bang-lin Luo; Hang Xing; Yong-chao Huang (Journal of Mountain Science, 2020)

The bacterial RNA ligase RtcB accelerates the repair process of fragmented rRNA upon releasing the antibiotic stress - Muhammad Ramzan Manwar; Changjun Shao; Xing Shi; Jian Wang; Qiang Lin; Yigang Tong; Yu Kang; Jun Yu (Science China Life Sciences, 2020)

One-step generation of zebrafish carrying a conditional knockout-knockin visible switch via CRISPR/Cas9-mediated intron targeting - Jia Li; Hong-Yu Li; Shan-Ye Gu; Hua-Xing Zi; Lai Jiang; Jiu-Lin Du (Science China Life Sciences, 2020)

Agrobacterium-mediated genetic transformation of Chinese chestnut (Castanea mollissima Blume) - Zhi-lin Sun; Xiao Li; Wan Zhou; Jun-di Yan; Yue-rong Gao; Xiao-wei Li; Jia-chen Sun; Ke-feng Fang; Qing Zhang; Yu Xing; Ling Qin; Qing-qin Cao (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)
Chinese chestnut ( Castanea mollissima ) is an important germplasm resource for the breeding of Castanea species worldwide with vital ecological and economic value. Biotechnology overcomes the limitations of traditional breeding and accelerates germplasm improvement. However, a genetic transformation system for Chinese chestnut has not yet been established. In this study, a stable and efficient Agrobacterium -mediated genetic transformation method for Chinese chestnut is described. Embryogenic calli of C. mollissima cv. ‘Yanshanhongli’ were used as the target material. The sensitivity of embryogenic calli to kanamycin was determined, whereby the proliferation of non-transformed calli was completely inhibited at 180 mg/L. Antibiotic inhibition results for Chinese chestnut embryogenic calli showed that 50 mg/L cefotaxime and 500 μM timentin completely inhibited the growth of Agrobacterium tumefaciens but did not affect the normal growth of Chinese chestnut embryogenic calli. When embryogenic calli were co-cultured for 2 days with Agrobacterium tumefaciens strain AGL1 harboring the PBI121-EGFP plasmid, an embryogenic callus transformation efficiency of 4.55% was obtained, and two transgenic chimera were acquired. This Agrobacterium -mediated transformation system for Chinese chestnut provides a fundamental platform for genetic improvement of core germplasm and for further verification of gene function.

Biogeochemical responses of soil ecosystems to raw coal pollution in Xuanhua, China - Yu Liu; Wu Xiang; Jie Zhu; Xiu-Zhi Zhang; Xu-Dong Xing; Wei-Lin Yang (Journal of Soils and Sediments, 2020)

C, N, and P stoichiometry and their interaction with different plant communities and soils in subtropical riparian wetlands - Meng-Fei Yu; Yongxia Tao; Wenzhi Liu; Wei Xing; Guihua Liu; Lai Wang; Lin Ma (Environmental Science and Pollution Research, 2020)

Characterization of the complete chloroplast genome of Euryodendron excelsum (Pentaphylacaceae), a critically endangered species endemic to China - Xiang-gang Shi; Wei-xi Li; Fen Xing; Yu-bin Zhou; Wu-xia Guo; Ye-lin Huang (Conservation Genetics Resources, 2019)

Isochromanes from Aspergillus fumigatus , an endophytic fungus from Cordyceps sinensis - Xiao-Hua Li; Xue-Hua Han; Ling-Ling Qin; Jun-Lin He; Zhi-Xing Cao; Yu-Cheng Gu; Da-Le Guo; Yun Deng (Natural Product Research, 2019)

Techniques for detecting protein-protein interactions in living cells: principles, limitations, and recent progress - Yaning Cui; Xi Zhang; Meng Yu; Yingfang Zhu; Jingjing Xing; Jinxing Lin (Science China Life Sciences, 2019)

l-Carnitine inhibits the senescence-associated secretory phenotype of aging adipose tissue by JNK/p53 pathway - Lian-wei Yang; Ming Song; Yu-lin Li; Ya-peng Liu; Chun Liu; Lu Han; Zhi-hao Wang; Wei Zhang; Yan-qiu Xing; Ming Zhong (Biogerontology, 2019)

Spatial variability of macrobenthic production in the Bering Sea - Heshan Lin; Kun Liu; Jianjun Wang; Junhui Lin; Yaqin Huang; Xuebao He; Zhong Li; Shuyi Zhang; Jianfeng Mou; Yanguang Liu; Puqing Song; Yu Wang; et al. (Polar Biology, 2019)

Intraguild predation between Harmonia axyridis and Aphidius gifuensis: effects of starvation period, plant dimension and extraguild prey density - Xing-Lin Yu; Yi Feng; Wen-Yan Fu; Yuan-Xing Sun; Tong-Xian Liu (BioControl, 2019)

Ornithinimicrobium cavernae sp. nov., an actinobacterium isolated from a karst cave - Ling-Yu Zhang; Hong Ming; Xiao-Lin Meng; Bao-Zhu Fang; Jian-Yu Jiao; Nimaichand Salam; Xiao-Tong Zhang; Wen-Jun Li; Guo-Xing Nie (Antonie van Leeuwenhoek, 2019)

PEGylated lipid microspheres loaded with cabazitaxel for intravenous administration: stability, bioavailability, antitumor efficacy, and toxicity - Yang Liu; Bin Xie; Lin Li; Xinyu Zhang; Yu Zhang; Haibing He; Tian Yin; Xing Tang; Cuifang Cai; Jingxin Gou (Drug Delivery and Translational Research, 2018)

A long-term tropical mesoscale convective systems dataset based on a novel objective automatic tracking algorithm - Xiaomeng Huang; Chenqi Hu; Xing Huang; Yang Chu; Yu-heng Tseng; Guang Jun Zhang; Yanluan Lin (Climate Dynamics, 2018)

Temporal and Spatial Variations of Microbial Carbon Utilization in Water Bodies from the Dajiuhu Peatland, Central China - Rui-Cheng Wang; Hong-Mei Wang; Xing Xiang; Yu Gao; Qing-Wei Song; Lin-Feng Gong (Journal of Earth Science, 2018)

Mixed Cadzow filtering method in fractional Fourier domain - Zhong-Lin Cao; Jun-Xing Cao; Fu-Rong Wu; Guang-Ming He; Qiang Zhou; Yu-Lin Wu (Applied Geophysics, 2018)

Spatial pattern of macrobenthic communities along a shelf-slope-basin transect across the Bering Sea - Heshan Lin; Kun Liu; Jianjun Wang; Yaqin Huang; Zhong Li; Junhui Lin; Xuebao He; Shuyi Zhang; Jianfeng Mou; Yu Wang; Bingpeng Xing (Acta Oceanologica Sinica, 2018)

Age-related changes of yolk precursor formation in the liver of laying hens - Xing-ting Liu; Xin Lin; Yu-ling Mi; Wei-dong Zeng; Cai-qiao Zhang (Journal of Zhejiang University-SCIENCE B, 2018)

Phylogenetic analysis of IRIS L. from China on chloroplast TRNL-F sequences - Yu-Lin Jiang; Zhuo Huang; Jin-Qiu Liao; Hui-Xing Song; Xiao-Mei Luo; Su-Ping Gao; Ting Lei; Ming-Yan Jiang; Yin Jia; Qi-Bing Chen; Xiao-Fang Yu; Yong-Hong Zhou (Biologia, 2018)

Hsp90 regulation affects the treatment of glucocorticoid for pancreatitis-induced lung injury - Yan Zhao; Ren-Ping Xiong; Xing Chen; Ping Li; Ya-Lei Ning; Nan Yang; Yan Peng; Yu-Lin Jiang; Yuan-Guo Zhou (Molecular and Cellular Biochemistry, 2018)

Characterization and fine mapping of qkc7.03: a major locus for kernel cracking in maize - Mingtao Yang; Lin Chen; Xun Wu; Xing Gao; Chunhui Li; Yanchun Song; Dengfeng Zhang; Yunsu Shi; Yu Li; Yong-xiang Li; Tianyu Wang (Theoretical and Applied Genetics, 2018)

Glycosaminoglycans from bovine eye vitreous humour and interaction with collagen type II - Yanfei Peng; Yanlei Yu; Lei Lin; Xinyue Liu; Xing Zhang; Peipei Wang; Pauline Hoffman; So Young Kim; Fuming Zhang; Robert J. Linhardt (Glycoconjugate Journal, 2018)

Glycosaminoglycans from fish swim bladder: isolation, structural characterization and bioactive potential - Yongxi Pan; Peipei Wang; Fuming Zhang; Yanlei Yu; Xing Zhang; Lei Lin; Robert J. Linhardt (Glycoconjugate Journal, 2018)

Erratum to: Matrine Treatment Blocks NogoA-Induced Neural Inhibitory Signaling Pathway in Ongoing Experimental Autoimmune Encephalomyelitis - Quan-Cheng Kan; Hui-Jun Zhang; Yuan Zhang; Xing Li; Yu-Ming Xu; Rodolfo Thome; Ming-Liang Zhang; Nan Liu; Yao-Juan Chu; Guang-Xian Zhang; Lin Zhu (Molecular Neurobiology, 2017)

Matrine Treatment Blocks NogoA-Induced Neural Inhibitory Signaling Pathway in Ongoing Experimental Autoimmune Encephalomyelitis - Quan-Cheng Kan; Hui-Jun Zhang; Yuan Zhang; Xing Li; Yu-Ming Xu; Rodolfo Thome; Ming-Liang Zhang; Nan Liu; Yao-Juan Chu; Guang-Xian Zhang; Lin Zhu (Molecular Neurobiology, 2017)

Nocardia tengchongensis sp. nov., isolated from a soil sample - Shuai Li; Hong Ming; Yan-Yan Duan; Jian-Rong Huang; Zhuo-Li Zhao; Ling-Yu Zhang; Wei-Li Ji; Xiao-Lin Meng; Wen-Jun Li; Guo-Xing Nie (Antonie van Leeuwenhoek, 2017)

Metformin Improves Functional Recovery After Spinal Cord Injury via Autophagy Flux Stimulation - Di Zhang; Jun Xuan; Bin-bin Zheng; Yu-long Zhou; Yan Lin; Yao-sen Wu; Yi-fei Zhou; Yi-xing Huang; Quan Wang; Li-yan Shen; Cong Mao; Yan Wu; et al. (Molecular Neurobiology, 2017)

PM2.5 emissions from different types of heavy-duty truck: a case study and meta-analysis of the Beijing-Tianjin-Hebei region - Liying Song; Hongqing Song; Jingyi Lin; Cheng Wang; Mingxu Yu; Xiaoxia Huang; Yu Guan; Xing Wang; Li Du (Environmental Science and Pollution Research, 2017)

Use of electroacupuncture and transcutaneous electrical acupoint stimulation in reproductive medicine: a group consensus - Fan Qu; Rong Li; Wei Sun; Ge Lin; Rong Zhang; Jing Yang; Li Tian; Guo-gang Xing; Hui Jiang; Fei Gong; Xiao-yan Liang; Yan Meng; et al. (Journal of Zhejiang University-SCIENCE B, 2017)

Branched polymeric prodrug/programmed cell death 4 complexes for combinational cancer therapy - Yu-Jing He; Lei Xing; Peng-Fei Cui; Jia-Liang Zhang; Jian-Bin Qiao; Cheng-Qiong Luo; Ge Jiang; Hu-Lin Jiang (Journal of Pharmaceutical Investigation, 2017)

Molecular signal networks and regulating mechanisms of the unfolded protein response - Jing Gong; Xing-zhi Wang; Tao Wang; Jiao-jiao Chen; Xiao-yuan Xie; Hui Hu; Fang Yu; Hui-lin Liu; Xing-yan Jiang; Han-dong Fan (Journal of Zhejiang University-SCIENCE B, 2017)

Multi-resolution graph-based clustering analysis for lithofacies identification from well log data: Case study of intraplatform bank gas fields, Amu Darya Basin - Yu Tian; Hong Xu; Xing-Yang Zhang; Hong-Jun Wang; Tong-Cui Guo; Liang-Jie Zhang; Xing-Lin Gong (Applied Geophysics, 2016)

Deep-Water Sedimentary Characteristics and Response in the Reed Area of the Southern South China Sea - Zheng Hong-Bo; Yan Pin; Yan-Lin Wang; Yu-Qing Xing (Marine Georesources & Geotechnology, 2016)

Using hybrid transcription factors to study gene function in rice - Tao Zhao; Jun Liu; Hong-Yu Li; Jian-Zhong Lin; Ming-Di Bian; Chun-Yu Zhang; Yong-Xing Zhang; Yu-Chong Peng; Bin Liu; ChenTao Lin (Science China Life Sciences, 2015)

A Uniform Ultra-Small Microsphere/SAIB Hybrid Depot with Low Burst Release for Long-Term Continuous Drug Release - Xia Lin; Yuhong Xu; Xing Tang; Yan Zhang; Jian Chen; Yu Zhang; Haibing He; Ziyi Yang (Pharmaceutical Research, 2015)

Voriconazole: a novel treatment option for cryptococcal meningitis - Yan Yao; Jia-Tang Zhang; Bo Yan; Ting Gao; Xiao-Wei Xing; Cheng-Lin Tian; Xu-Sheng Huang; Sheng-Yuan Yu (Infectious Diseases, 2015)

Retraction Note to: Analyzing time-series microarray data reveals key genes in spinal cord injury - Xun Xia; Bo Qu; Yuan Ma; Li-bin Yang; Hai-dong Huang; Jing-ming Cheng; Tao Yang; Bin Kong; En-yu Liu; Kai Zhao; Wei-qi He; Xue-min Xing; et al. (Molecular Biology Reports, 2015)

A Novel Oral Preparation of Hydroxysafflor Yellow A Base on a Chitosan Complex: A Strategy to Enhance the Oral Bioavailability - Guan-nan Ma; Fang-lin Yu; Shan Wang; Zhi-ping Li; Xiang-yang Xie; Xing-guo Mei (AAPS PharmSciTech, 2015)

Cytokine production suppression by culture supernatant of B16F10 cells and amelioration by Ganoderma lucidum polysaccharides in activated lymphocytes - Li-Xin Sun; Wei-Dong Li; Zhi-Bin Lin; Xin-Suo Duan; En-Hong Xing; Miao-Miao Jiang; Ning Yang; Hai-Hua Qi; Yu Sun; Min Li; Yan-Dong Niu; Jie Lu (Cell and Tissue Research, 2015)

A putative soybean GmsSOS1 confers enhanced salt tolerance to transgenic Arabidopsis sos1-1 mutant - Wang-xing Nie; Lin Xu; Bing-jun Yu (Protoplasma, 2015)

RETRACTED ARTICLE: Analyzing time-series microarray data reveals key genes in spinal cord injury - Xun Xia; Bo Qu; Yuan Ma; Li-bin Yang; Hai-dong Huang; Jing-ming Cheng; Tao Yang; Bin Kong; En-yu Liu; Kai Zhao; Wei-qi He; Xue-min Xing; et al. (Molecular Biology Reports, 2014)

ROCK inhibition prevents early mouse embryo development - Xing Duan; Kun-Lin Chen; Yu Zhang; Xiang-Shun Cui; Nam-Hyung Kim; Shao-Chen Sun (Histochemistry and Cell Biology, 2014)

Quantitative trait loci analysis of individual and total isoflavone contents in soybean seeds - HAI JUN ZHANG; JING WEN LI; YA JING LIU; WEN ZHU JIANG; XING LIN DU; LIN LI; XIAO WEI Li; LIAN TAI SU; QING YU WANG; YING WANG (Journal of Genetics, 2014)

Menstrual blood-derived mesenchymal stem cells differentiate into functional hepatocyte-like cells - Xiao-zhou Mou; Jian Lin; Jin-yang Chen; Yi-fei Li; Xiao-xing Wu; Bing-yu Xiang; Cai-yun Li; Ju-ming Ma; Charlie Xiang (Journal of Zhejiang University-SCIENCE B, 2013)

New Evidence for the Role of Ethylene in Strawberry Fruit Ripening - Jing-Hua Sun; Jing-Jing Luo; Lin Tian; Chun-Li Li; Yu Xing; Yuan-Yue Shen (Journal of Plant Growth Regulation, 2013)

Functional analyses of a flavonol synthase–like gene from Camellia nitidissima reveal its roles in flavonoid metabolism during floral pigmentation - Xing-Wen Zhou; Zheng-Qi Fan; Yue Chen; Yu-Lin Zhu; Ji-Yuan Li; Heng-Fu Yin (Journal of Biosciences, 2013)

Selenium Attenuates Adriamycin-Induced Cardiac Dysfunction via Restoring Expression of ATP-Sensitive Potassium Channels in Rats - Zhong-Wei Liu; Xiao-Lin Niu; Kun-Lun Chen; Yu-Jie Xing; Xuan Wang; Chuan Qiu; Deng-Feng Gao (Biological Trace Element Research, 2013)

Quantitative evaluation of Candia antarctica lipase B displayed on the cell surface of a Pichia pastoris based on an FS anchor system - Xing-xiang Liang; Bei-bei Wang; Yu-fei Sun; Ying Lin; Shuang-yan Han; Sui-ping Zheng; Tang-bing Cui (Biotechnology Letters, 2013)

Dorsal root ganglion compression as an animal model of sciatica and low back pain - Xiao-Yu Lin; Jing Yang; Hui-Ming Li; San-Jue Hu; Jun-Ling Xing (Neuroscience Bulletin, 2012)

Identification, fine mapping and characterization of Rht-dp, a recessive wheat dwarfing (reduced height) gene derived from Triticum polonicum - Hou-Yang Kang; Li-Juan Lin; Zhi-Jian Song; Jing-Ya Yuan; Mei-Yu Zhong; Hai-Qin Zhang; Xing Fan; Li-Na Sha; Yi Wang; Li-Li Xu; Jian Zeng; Yong-Hong Zhou (Genes & Genomics, 2012)

Time-dependent expression and distribution of Egr-1 during skeletal muscle wound healing in rats - Yan-Yan Fan; Guang-Hua Ye; Ke-Zhi Lin; Lin-Sheng Yu; Shu-Zhen Wu; Miao-Wu Dong; Jun-Ge Han; Xiang-Ping Feng; Xing-Biao Li (Journal of Molecular Histology, 2012)

Interaction between iron plaque and root border cells ameliorates aluminum toxicity of Oryza sativa differing in aluminum tolerance - Miao-Zhen Cai; Shu-Na Zhang; Cheng-Hua Xing; Fang-Mei Wang; Lei Zhu; Ning Wang; Li-Yu Lin (Plant and Soil, 2012)

Alleviative effect of quercetin on germ cells intoxicated by 3-methyl-4-nitrophenol from diesel exhaust particles - Tong-liang Bu; Yu-dong Jia; Jin-xing Lin; Yu-ling Mi; Cai-qiao Zhang (Journal of Zhejiang University-SCIENCE B, 2012)

Immobilization of foreign protein into polyhedra of Bombyx mori nucleopolyhedrovirus (BmNPV) - Xing-wei Xiang; Rui Yang; Lin Chen; Xiao-long Hu; Shao-fang Yu; Cui-ping Cao; Xiao-feng Wu (Journal of Zhejiang University-SCIENCE B, 2012)

Effect of epidermal growth factor on follicle-stimulating hormone-induced proliferation of granulosa cells from chicken prehierarchical follicles - Jin-xing Lin; Yu-dong Jia; Cai-qiao Zhang (Journal of Zhejiang University-SCIENCE B, 2011)

Interaction of green tea polyphenol epigallocatechin-3-gallate with sunitinib: potential risk of diminished sunitinib bioavailability - Jun Ge; Ben-Xu Tan; Ye Chen; Li Yang; Xing-Chen Peng; Hong-Ze Li; Hong-Jun Lin; Yu Zhao; Meng Wei; Ke Cheng; Long-Hao Li; Hang Dong; et al. (Journal of Molecular Medicine, 2011)

Development and characterization of wheat-Psathyrostachys huashanica partial amphiploids for resistance to stripe rust - Yi Wang; Quan Xie; Kangyu Yu; Vaino Poysa; Lijuan Lin; Houyang Kang; Xing Fan; Lina Sha; Haiqin Zhang; Yonghong Zhou (Biotechnology Letters, 2011)

Bioavailability Study of Berberine and the Enhancing Effects of TPGS on Intestinal Absorption in Rats - Wei Chen; Yu-Qiang Miao; Dong-Jiao Fan; Shen-Shen Yang; Xia Lin; Ling-Kuo Meng; Xing Tang (AAPS PharmSciTech, 2011)

Do higher resource capture ability and utilization efficiency facilitate the successful invasion of native plants? - Xing-Yan Shen; Shao-Lin Peng; Bao-Ming Chen; Jun-Xiao Pang; Lei-Yi Chen; Hao-Ming Xu; Yu-Ping Hou (Biological Invasions, 2011)

Over-expression of the AtGA2ox8 gene decreases the biomass accumulation and lignification in rapeseed (Brassica napus L.) - Xiao-ying Zhao; Deng-feng Zhu; Bo Zhou; Wu-sheng Peng; Jian-zhong Lin; Xing-qun Huang; Re-qing He; Yu-hong Zhuo; Dan Peng; Dong-ying Tang; Ming-fang Li; Xuan-ming Liu (Journal of Zhejiang University-SCIENCE B, 2010)

Chloroplast transformation of rapeseed (Brassica napus) by particle bombardment of cotyledons - Lin Cheng; He-Ping Li; Bo Qu; Tao Huang; Jin-Xing Tu; Ting-Dong Fu; Yu-Cai Liao (Plant Cell Reports, 2010)

Human papillomavirus type-distribution in cervical cancer in China: the importance of HPV 16 and 18 - Wen Chen; Xun Zhang; Anco Molijn; David Jenkins; Ju-Fang Shi; Wim Quint; Johannes E. Schmidt; Ping Wang; Yu-Ling Liu; Lian-Kun Li; Hong Shi; Ji-Hong Liu; et al. (Cancer Causes & Control, 2009)

Polymorphisms within promoter of Japanese flounder (Paralichthys olivaceus) ovary cytochrome P450-c19 (CYP19a) gene associated with reproductive traits - Feng He; Hai Shen Wen; Shuang Lin Dong; Bao Shi; Cai Fang Chen; Lian Shun Wang; Jun Yao; Xing Jiang Mu; Yu Guo Zhou (Fish Physiology and Biochemistry, 2009)

The block of intracellular calcium release affects the pollen tube development of Picea wilsonii by changing the deposition of cell wall components - Kun-Ming Chen; Guo-Li Wu; Yu-Hua Wang; Cui-Ting Tian; Jozef Šamaj; František Baluška; Jin-Xing Lin (Protoplasma, 2008)

Purification and characterization of a novel neutral β-glucanase and an alkaline β-glucanase from an alkaliphilic Bacillus isolate - Sen-Lin Liu; Wei-Zhao Chen; Yong Wang; Gang Liu; Shao-Wen Yu; Miao Xing (World Journal of Microbiology and Biotechnology, 2008)

Localization of vesicular glutamate transporters in the peripheral vestibular system of rat - Yuan Wang; You-Wang Pang; Yu-Lin Dong; Fu-Xing Zhang; Jin-Lian Li; Yun-Qing Li (Neuroscience Bulletin, 2007)

Mutation analysis of 218 Chinese patients with Wilson disease revealed no correlation between the canine copper toxicosis gene MURR1 and Wilson disease - Zhi-Ying Wu; Gui-Xian Zhao; Wan-Jin Chen; Ning Wang; Bo Wan; Min-Ting Lin; Shen-Xing Murong; Long Yu (Journal of Molecular Medicine, 2006)

A common IL-13 Arg130Gln single nucleotide polymorphism among Chinese atopy patients with allergic rhinitis - Min Wang; Zhi-Min Xing; Chao Lu; You-Xiang Ma; De-Lin Yu; Zheng Yan; Shen-Wu Wang; Li-Sheng Yu (Human Genetics, 2003)